Filter media comprising fine fiber layer
A multi-layered filter media with a support layer, continuous fine fiber layer, and efficiency layer addresses efficiency drops under dynamic flow conditions by maintaining pressure drop, enhancing filtration performance and system longevity.
Patent Information
- Application Number
- CN202411189384.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-04-03
- Filing Date
- 2020-10-08
- Publication Date
- 2024-12-27
AI Technical Summary
Filter media efficiency is adversely affected by changes in flow rate during hydraulic applications, leading to increased pressure drop and reduced performance under dynamic conditions.
A filter media comprising a support layer, a continuous fine fiber layer, and an efficiency layer, with specific P95/P50 ratios and layer configurations, minimizes the adverse effects of flow rate changes without increasing pressure drop.
The filter media maintains efficiency under variable flow conditions while keeping pressure drop within acceptable limits, extending the life of hydraulic systems and improving filtration performance.
Smart Images

Figure CN119186108A_ABST
Abstract
Description
CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application claims the benefit of the following U.S. provisional applications: U.S. provisional application serial number 62 / 912,456 filed on October 8, 2019; U.S. provisional application serial number 62 / 947,998 filed on December 13, 2019; U.S. provisional application serial number 62 / 952,979 filed on December 23, 2019; U.S. provisional application serial number 62 / 992,003 filed on March 19, 2020; and U.S. provisional application serial number 63 / 004,602 filed on April 3, 2020, the disclosures of the above U.S. provisional applications are incorporated herein by reference in their entirety. Summary of the invention
[0002] Filter media for hydraulic applications are typically tested at a steady flow rate. However, in many hydraulic applications, flow rates vary during use. Changes in flow rate, including, for example, under cyclic flow conditions or other dynamic flow conditions, have an adverse effect on filter media performance, and in particular, filter media efficiency, because changes in flow rate result in multiple opportunities for particles to pass through the media openings.
[0003] The present disclosure describes a filter media that minimizes the adverse effects of changes in flow rate on filter media efficiency without a corresponding increase in pressure drop, i.e., an increase in the pressure required to force a fluid through the filter media. Although it was known at the time of the present invention that the effects of varying flow rates on filter media performance could be minimized by increasing the efficiency of the filter media, the means for increasing the efficiency of the filter media also result in a corresponding increase in pressure drop. This increase in pressure drop results in more opportunities to bypass the filter (e.g., via a bypass valve), increased energy consumption, and shorter filter life. In contrast, the filter media described herein achieves an increase in efficiency without compromising pressure drop.
[0004] In one aspect, the present disclosure describes a filter media comprising: a support layer; a continuous fine fiber layer having a thickness of up to 50 μm; and an efficiency layer. The composite material comprising the support layer and the continuous fine fiber layer has a P95 / P50 ratio of up to 1.8, up to 1.9, or up to 2. The efficiency layer has a P95 / P50 ratio of at least 1.8, at least 1.9, or at least 2. Additionally, the P95 value of the composite material falls within the range provided by the P5 and P50 values of the efficiency layer.
[0005] In some embodiments, the composite material has a P95 / P50 ratio greater than 1.
[0006] In some embodiments, the continuous fine fiber layer has a thickness of at least 2 μm. In some embodiments, the continuous fine fiber layer is located between the efficiency layer and the support layer. In some embodiments, the continuous fine fiber layer includes fibers having a diameter of up to 10 microns (μm). In some embodiments, the continuous fine fiber layer includes fibers having an elliptical shape. In some embodiments, the continuous fine layer includes fibers having a diameter of at least 1 micron (μm).
[0007] In some embodiments, the continuous fine fiber layer includes a mixture of fibers of different diameters. Fibers of different diameters can be intermixed within a single layer of the continuous fine fiber layer. Additionally or alternatively, fibers of different diameters can form different layers in the continuous fine fiber layer.
[0008] In some embodiments, the efficiency layer has a P95 / P50 ratio of up to 10, up to 15, or up to 20. In some embodiments, the efficiency layer is located on the upstream side of the filter media.
[0009] In some embodiments, the filter media further includes a second efficiency layer.The second efficiency layer can be adjacent to and upstream of the efficiency layer.
[0010] In some embodiments, the efficiency layer comprises bicomponent fibers and efficiency fibers, wherein the efficiency fibers have a smaller diameter than the bicomponent fibers. The efficiency fibers may comprise glass fibers. In some embodiments, the efficiency layer comprises microfibrillated cellulose fibers.
[0011] In some embodiments, the support layer may include a spunbond layer.
[0012] In another aspect, the present disclosure describes a filter element that includes the filter media described herein.In some embodiments, a wire support can be located downstream of the support layer.
[0013] As used herein, "fibers" have an average fiber diameter of up to 100 microns.
[0014] As used herein, a fiber with an "average" diameter indicates that, in a sample of a plurality of fibers, the average fiber diameter of the fiber population in the sample has the indicated average fiber diameter. The fiber population includes fibers having a diameter within 25% of the average fiber diameter. For example, a fiber population having an average diameter of 1000 nm includes fibers having a diameter of at least 750 nm and up to 1250 nm. In another example, a fiber population having an average diameter of 250 nm includes fibers having a diameter of at least 188 nm and up to 313 nm. In a further example, a fiber population having an average diameter of 500 nm includes fibers having a diameter of at least 375 nm and up to 625 nm. In yet another example, a fiber population having an average diameter of 1400 nm includes fibers having a diameter of at least 1050 nm and up to 1750 nm.
[0015] The fiber diameter can be measured using a top-down SEM image. The sample can be sputter coated. A useful sputter coater can be a gold and palladium mixture, which includes, for example, a mixture of 60:40 Au:Pd. By measuring the diameter of the fiber in at least 30 positions in the sample, a more accurate fiber diameter measurement can be obtained. Software such as Trainable WekaSegmentation (ImageJ plugin) may be useful for analyzing fiber diameter.
[0016] As used herein, "thin fibers" refers to fibers having a diameter of up to 10 micrometers (μm). In some embodiments, the diameter of the thin fibers is at least 50 nm or at least 100 nm.
[0017] The term "diameter" refers to either the diameter of a circular cross-section of a fiber or the largest cross-sectional dimension of a non-circular cross-section of a fiber.
[0018] As used herein, the term "particle size" refers to the diameter of a particle determined as described in ISO 11171:2016.
[0019] As used herein, "continuous fine fibers" refers to fine fibers having an aspect ratio (i.e., length to transverse dimension) of at least 5,000, or more preferably at least 10,000. References herein to a continuous fine fiber layer refer to a layer comprising continuous fine fibers (as opposed to chopped fine fibers). While the continuous fine fiber layer is preferably formed by a fiber-forming process that produces continuous fine fibers, the resulting layer may or may not include only one type of continuous fine fiber. That is, the continuous fine fiber layer may include one or more fine fibers that are shaved to an aspect ratio of at least 5,000, or more preferably at least 10,000.
[0020] As used herein, "chopped strands" refer to strands having an aspect ratio (ie, length to transverse dimension) of less than 5,000, less than 2,500, or less than 1,000. Typically, the aspect ratio of the chopped strands is at least 10 and up to 5,000.
[0021] As used herein, "hybrid" fibers or "hybrid fiber structure" refers to fibers having at least two different diameters, wherein fibers having an average first diameter and fibers having an average second diameter are intermixed, i.e., wherein the fibers are mixed within the same layer (or stratum) of the media structure because the fibers have been formed or deposited simultaneously, or by using very short (e.g., up to 10 seconds, up to 20 seconds, or up to 30 seconds) pulses of each polymer solution. When visualized using a top-down SEM image, fibers having an average first diameter can be observed to be both below and above fibers having an average second diameter.
[0022] As used herein, "layered" fibers or a "layered fibrous structure" refers to fibers having at least two different diameters, wherein fibers having an average first diameter are substantially unentangled with fibers having an average second diameter because the fibers of different diameters have been alternately applied to a substrate.
[0023] As used herein, unless otherwise indicated, capillary flow porosimetry is used to determine pore sizes (e.g., P5, P50, and P95) and ratios of pore sizes (e.g., P95 / P50). Capillary flow porosimetry can be performed using a continuous pressure scan mode. It can be useful to use silicone oil with a surface tension of 20.1 dynes / cm and a wetting contact angle of 0 as a wetting fluid. The sample can be initially tested in a dry state (low pressure is changed to high pressure) and then tested in a wet state (low pressure is changed to high pressure again). The test is typically performed under ambient temperature conditions (e.g., 20°C to 25°C). For both dry and wet curves, 256 data points can be collected across the scan range of pressure. Typically, tortuosity factors and / or shape factors will not be used (i.e., a factor equal to 1 can be used to compare with other test methods using adjustment factors).
[0024] As used herein, the value P(x%) is the calculated pore size when the wet curve equals (100-x)% of the dry curve, as determined using the methods described herein. Although a calculated value, this can be understood to represent the point at which x% of the total flow through the layer passes through pores of that size or less. For example, P50 (mean flow pore size) represents the point at which the wet curve equals half of the dry curve, and can be considered to be the pore size such that 50% of the total flow through the layer passes through pores of that size or less.
[0025] The average pore size (e.g., average maximum pore size) can be calculated from the average of at least three measurements (obtained from at least three different sample locations). A single measurement of the maximum pore size (which may also be referred to as P100) can be detected at the bubble point, where the bubble point is found after the fluid begins to pass through the sample and three consecutive measurements increase by at least 1%, where 256 data points are collected over the entire scan at a rate of approximately 17 data points per minute.
[0026] As used herein, the "beta ratio" (also referred to herein as "β" or "Beta ratio") is the ratio of upstream particles to downstream particles. The higher the filter efficiency, the higher the beta ratio. The beta ratio is defined as follows:
[0027] Where N d,U is the upstream particle count per unit fluid volume of particles with diameter d or larger, and N d,D is the downstream particle count per unit fluid volume of particles of diameter d or larger. If present, the subscript attached to β indicates the particle size for which the ratio is being reported.
[0028] As used herein, the "total beta ratio" or "total beta" is the ratio of the sum of all upstream particles during the determination to the sum of all downstream particles during the test (where the test is run at a pressure of 25 psi (172 kPa)):
[0029] Where N d,U is the upstream particle count per unit fluid volume of particles with diameter d or larger, and N d,D is the downstream particle count per unit fluid volume of particles of diameter d or larger. If present, the subscript attached to β indicates the particle size for which the ratio is being reported.
[0030] As used herein, "β100" is the particle size at which the total β is 100.
[0031] As used herein, "filtration efficiency" or "efficiency" refers to the percentage of contaminants removed by a filter, which is calculated as follows:
[0032] Where e is the filtration efficiency, and β is defined as indicated above. Therefore, the efficiencies referred to herein are cumulative efficiencies. If present, the subscript attached to e indicates the particle size for which the ratio is being reported.
[0033] As used herein, "pressure drop" (also referred to herein as "dP" or "ΔP") relates to the pressure (applied by a pump) required to force a fluid through a filter or filter media (before adding contaminants) for a specific fluid velocity. Unless otherwise indicated, pressure drop is measured as described in ISO 3968:2017.
[0034] Where the term "comprising" and its variations appear in the specification and claims, these terms are not intended to have a restrictive meaning. Such terms will be understood to imply the inclusion of a stated step or element or a set of steps or elements, but not to exclude any other step or element or a set of steps or elements. "Consisting of" means including and limited to whatever follows the phrase "consisting of". Thus, the phrase "consisting of" indicates that the listed elements are required or mandatory, and that other elements may not be present. "Consisting essentially of" means including any element listed after the phrase, and is limited to other elements that do not interfere with or contribute to the functions or effects specified for the listed elements in the present disclosure. Thus, the phrase "consisting essentially of" indicates that the listed elements are required or mandatory, but other elements are optional and may or may not exist, depending on whether they substantially affect the functions or effects of the listed elements.
[0035] The words "preferred" and "preferably" refer to embodiments of the present invention that may provide certain benefits in certain circumstances. However, other embodiments may also be preferred under the same or other circumstances. In addition, the recitation of one or more preferred embodiments does not imply that other embodiments are not useful, and is not intended to exclude other embodiments from the scope of the present invention.
[0036] Unless otherwise specified, "a / an", "the", and "at least one" are used interchangeably and mean one or more than one. The phrases "at least one of" and "including at least one of" preceding a list refer to any one of the items in the list and any combination of two or more of the items in the list.
[0037] As used herein, the term "or" is generally employed in its ordinary sense including "and / or" unless the context clearly dictates otherwise. The term "and / or" means one or all of the listed elements or a combination of any two or more of the listed elements.
[0038] Also herein, the recitation of numerical ranges by endpoints includes all numbers subsumed within that range (e.g., 1 to 5 includes 1, 1.5, 2, 2.75, 3, 3.80, 4, 5, etc.). As used herein, "up to" a number (e.g., up to 50) includes that number (e.g., 50).
[0039] For any method disclosed herein that includes discrete steps, the steps may be performed in any practicable order. Also, any combination of two or more steps may be performed simultaneously, where appropriate.
[0040] References throughout this specification to "one embodiment," "an embodiment," "certain embodiments," or "some embodiments," etc., mean that a particular feature, configuration, composition, or characteristic described in connection with the embodiment is included in at least one embodiment of the present disclosure. Thus, the appearance of such a phrase in various places throughout this specification is not necessarily referring to the same embodiment of the present disclosure. Furthermore, in one or more embodiments, the particular features, configurations, compositions, or characteristics may be combined in any suitable manner.
[0041] Unless otherwise indicated, any reference to a standard method (eg, ASTM, TAPPI, AATCC, etc.) refers to the most recent available version of that method at the time of filing of this disclosure.
[0042] Unless otherwise indicated, all digits expressing the amount of components, molecular weight, etc. used in the specification and claims will be understood to be modified by the term "about" in all cases. As used herein in conjunction with the measured amount, the term "about" refers to the variation of the measured amount, as expected by the technician who performs the measurement and operates with a cautious level commensurate with the accuracy of the measurement purpose and the measurement equipment used. Therefore, unless otherwise indicated to the contrary, the numerical parameters set forth in the specification and claims are approximate values, which may vary depending on the desired properties sought to be obtained by the present invention. At least, and not attempting to limit the scope of the claims, the doctrine of equivalents, each numerical parameter should at least be interpreted according to the reported significant digits and by applying general rounding techniques.
[0043] Notwithstanding that the numerical ranges and parameters setting forth the broad scope of the invention are approximations, the numerical values set forth in the specific examples are reported as precisely as possible. However, all numerical values inherently contain the range necessarily resulting from the standard deviation found in their respective testing measurements.
[0044] All headings are for the convenience of the reader and should not be used to limit the meaning of the text that follows the heading unless so specified.
[0045] The above summary of the present invention is not intended to describe each disclosed embodiment or each implementation of the present invention. The following description more specifically illustrates illustrative embodiments. In several places throughout this application, guidance is provided by lists of examples, which can be used in various combinations. In each case, the narrated lists serve only as representative groups and should not be construed as exclusive lists. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1A to Figure 1B Exemplary filter media and filter element configurations are shown, as further described herein.
[0047] Figure 2A A schematic diagram of an exemplary embodiment of a continuous fine fiber layer of a filter media described herein that includes a mixture of fibers of different diameters in different layers of the continuous fine fiber layer is shown. Figure 2B Exemplary images of a continuous fine fiber layer including a fine fiber layer deposited on a nylon scrim are shown at 500x magnification (top portion) and 2000x magnification (bottom portion). Figure 2C An exemplary SEM image (1000x magnification) of a sample prepared as described in Example 3 (comprising a continuous fine fiber layer of small fine fibers laid directly on a scrim) is shown. Figure 2D An exemplary SEM image (1000x magnification) of a sample prepared as described in Example 3 (comprising a continuous fine fiber layer of small fine fibers overlying large fine fibers) is shown. Figure 2E Exemplary SEM images (1000x magnification) of continuous fine fiber layer samples are shown, which are prepared using Solution 1 as described in Example 4 to achieve small fine fibers (left panel), prepared using Solution 1 and Solution 2 to achieve mixed fine fibers of mixed (small and large) diameters (center panel), and prepared using Solution 2 to achieve large fine fibers (right panel). Figure 2F A schematic diagram of a sample prepared as described in Example 3 (small fine fibers laid directly on the scrim) is shown. Figure 2G A schematic diagram of a continuous fine fiber layer sample prepared as described in Example 3 (small fine fibers overlaying large fine fibers, which are laid directly on a scrim) is shown. Figures 2H to 2M Schematic diagrams of exemplary media configurations are shown. In each configuration, the support layer is not shown, but it would typically be located on the downstream side of the media. In each configuration, the efficiency layer is not shown, but it would typically be located on the upstream side of the media.
[0048] Figure 3AThe beta ratio of three different media is shown as a function of particle size under circulating flow conditions (blue) or steady flow conditions (red). Left panel: Donaldson Synteq XP with 10 micron (μm) efficiency rating TM Synthetic liquid media. Center panel: Donaldson Synteq XP with 5 micron efficiency rating TM Synthetic liquid media. Right panel: Filter media as described in Example 1 (XP / fine fiber / scrim) (efficiency layer (Donaldson Synteq XP with 10 micron efficiency rating) TM synthetic liquid medium), a continuous fine fiber layer and a support layer (scrim). Figure 3B Shows Figure 3A The pressure drop of the same medium tested in .
[0049] Figure 4 Figure 2 shows the beta ratio versus particle size for filter elements under steady flow conditions, including the Donaldson Synteq XP with a 10 micron efficiency rating. TM Synthetic liquid media (top) or filter media as described in Example 2 (efficiency layer (Donaldson Synteq XP with 10 micron efficiency rating) TM The Beta Ratio is measured as described in the Steady Flow Conditions test. The three numbers separated by a slash indicate the International Organization for Standardization (ISO) cleanliness code measured and defined as described in ISO 4406:2017.
[0050] Figure 5 Figure 2 shows the beta ratio versus particle size for filter elements under circulating flow conditions, including the Donaldson Synteq XP with a 10 micron efficiency rating. TM Synthetic liquid media (top) or filter media as described in Example 2 (efficiency layer (Donaldson Synteq XP with 10 micron efficiency rating) TM Synthetic liquid media), continuous fine fiber layer, and support layer). In these examples, the Beta Ratio is measured as described in the Circular Flow Conditions test. The three numbers separated by a slash indicate the International Organization for Standardization (ISO) cleanliness code measured and defined as described in ISO 4406:2017.
[0051] FIG. 6A to FIG. 6B The maximum pore size ( Fig. 6A ) or the composite material mean flow pore size ( Figure 6B ) as further described in Example 5. Triangles represent samples that maintained the structural integrity of the fine fibers throughout the test; squares represent samples that suffered fine fiber bursting during the test.
[0052] Figure 7 The cumulative flow pore size distribution of the sample described in Example 6 is shown.
[0053] Fig. 8A An exemplary cross-sectional image of a continuous fine fiber layer on a support layer is shown. FIG. 8B to FIG. 8D An exemplary image is shown of a method for measuring the thickness of a continuous fine fiber layer, as further described in these examples. DETAILED DESCRIPTION
[0054] The present disclosure describes a filter media that minimizes the adverse effects of changes in flow rate (e.g., occurring during dynamic flow conditions) on filter media efficiency without a corresponding increase in pressure drop, i.e., an increase in the pressure required to force a fluid through the filter media. The present disclosure further describes methods of making the filter media. Challenges of Designing Filter Media for Dynamic Flow Conditions
[0055] The present disclosure describes a filter media that minimizes the adverse effects of changes in flow rate on filter media efficiency without a corresponding increase in pressure drop. These changes in flow rate may occur, for example, during dynamic flow conditions. Dynamic flow conditions include, for example, cyclic flow conditions. However, as further discussed herein, the filter media design may also be used to improve performance in other liquid applications.
[0056] If filters were designed with efficiency as the only performance criterion, all filtration needs would be easily addressed. However, for most applications, pressure and filter life must also be considered and balanced with the desired efficiency.
[0057] For example, it is easy to design a filter that removes 100% of all particles larger than 0.5 μm, but if the pressure required to push the fluid through the filter is unreasonably high, or if the filter needs to be replaced at impractically short intervals, then this filter design will not be practical. In a more specific example, even if the oil filter in your car keeps the engine perfectly clean, it will not be commercially and practically viable if that filter requires most of the engine's power to push the fluid through the filter and needs to be replaced every time the vehicle is refueled.
[0058] To provide an illustration of how the filter media described herein improve efficiency performance, it is helpful to first describe how the filter media collects contaminants and how this collection affects the pressure across the filter media as fluid flows through the filter media.
[0059] The filter media includes spaces between the components of the filter media, and it can also collect contaminants on the uppermost surface of the filter media. As contaminants collect in the spaces within or on top of the filter media, the pressure required to push the fluid across the filter media increases because the spaces for the fluid to flow through become smaller and fewer in number. The end of life of a working fluid filter media, especially in hydraulic devices, is often defined by the maximum pressure generated when a certain flow rate of liquid passes through the filter media. Therefore, as contaminants are collected, the pressure drop increases, and the porosity of the filter media (the ratio of the volume of spaces in a porous media to the total volume) decreases.
[0060] As porosity decreases, it becomes the primary contributor to pressure drop, and therefore the primary parameter that defines the end of life of a liquid filter. Therefore, in order to achieve longer life for hydraulic filter media, it is therefore desirable to manage how contaminants are collected by the filter media. Distributing the locations where contaminants are collected (including, for example, by making more space available throughout the depth of the media) rather than collecting contaminants in a single location (e.g., on the surface of the media) results in the porosity of the filter media being maintained longer, reducing the pressure required to move liquid through the media, and extending the life of the filter media. Filter media designs that distribute the locations where contaminants are collected across the depth of the media are referred to as depth-loaded filter media.
[0061] Higher porosity throughout the depth of the filter media allows for more space for contaminants to collect during the use of the filter media. It is hypothesized that the most durable filter media would be one with 100% porosity. But this advantage is only hypothetical, as some of the volume must be occupied by something in order to capture and hold contaminants. Therefore, it is desirable to have as high a porosity as possible while still providing a filter material with the properties necessary to achieve the desired efficiency and strength.
[0062] In liquid hydraulic filtration, the primary filtration mechanism is size exclusion. During size exclusion, contaminants are captured by the filter media when they are trapped in pores that are smaller in size than the contaminant. A broad distribution of pore sizes (throughout the depth of the filter media) allows the contaminants to be distributed within the thickness of the filter media. The pores may be randomly spaced, or they may form a gradient or other patterned structure. Regardless of the pattern (or lack thereof), the desired effect is to distribute the contaminants as far as possible throughout the depth of the filter media.
[0063] Filter media designed for collection by size exclusion have been shown in laboratory testing to work well under steady flow conditions. But in most hydraulic flow applications, the flow rate through the filter media is variable and may have a cyclic flow pattern. During these variable flow conditions, changing forces (more commonly referred to as dynamic forces) are exerted on both the filter media structure and the contaminants captured by the filter media. These dynamic forces change the way the filter media captures contaminants, resulting in a decrease in overall efficiency.
[0064] Without wishing to be bound by theory, it is believed that the overall reduction in efficiency observed during variable flow conditions is caused by contaminants that have been previously trapped in pores smaller in size than the contaminants being re-released when different forces are applied to the filter media.
[0065] As a result, filters rated to achieve a certain efficiency performance under steady flow conditions often perform poorly during variable (e.g., cyclic) flow conditions, and these filters allow more contaminants to pass through the filter into the downstream output. Increased contaminants downstream of the filter may cause increased wear in the hydraulic system and / or shorter life of key hydraulic components.
[0066] Therefore, users of these hydraulic systems desire to have hydraulic oil filtration media that is designed to perform reliably under variable flow conditions.
[0067] One means of improving media efficiency under variable flow conditions is to increase the thickness of the filter media. By providing increased thickness (or depth), more opportunities for capturing specific contaminants are provided. However, if the filter media becomes too thick, it becomes difficult to fit it into a limited space, such as a traditional pleated configuration. Furthermore, even if it is possible to improve the capture of a specific contaminant by increasing the thickness, the contaminant may still pass through the media.
[0068] Another means of increasing media efficiency under variable flow conditions is to reduce the pore size of the filter media. However, as described above, reducing the pore size causes the filter media to reach saturation more quickly. In addition, smaller pore sizes may result in greater pressures being required to force liquid through the media before contaminants are captured, and will certainly result in greater pressures being required to force liquid through the media after a certain volume of contaminants has been captured.
[0069] The filter media described herein seeks to overcome these limitations by providing a multi-layered structure.While each layer alone would perform poorly, the combination of layers provides improved performance under variable flow conditions, including, for example, cyclic flow conditions. Filter Media
[0070] In one aspect, the present disclosure describes a filter media comprising a support layer, a continuous fine fiber layer, and an efficiency layer. In some embodiments, the continuous fine fiber layer is located between the efficiency layer and the support layer, and the efficiency layer is located on the upstream side of the filter media. In some embodiments, the continuous fine fiber layer acts as a surface loading layer. In some embodiments, the efficiency layer acts as a depth loading layer.
[0071] As described above, the depth loading layer alone has low efficiency under variable flow conditions due to its low solidity and wide pore size distribution. If the continuous fine fiber layer alone served as the surface loading layer, it alone would have a very short life under variable flow conditions because the pressure required to move the liquid through the filter media would begin to increase almost immediately after the contaminants are collected. Also, the support layer alone would not be suitable for use as a filter media under variable flow conditions because its efficiency would be virtually non-existent.
[0072] However, in combination with selected features as further described herein, the support layer, continuous fine fiber layer, and efficiency layer provide a filter media that minimizes the adverse effects of variable flow conditions on filter media efficiency and does not exhibit commercially or practically unfeasible increases in pressure drop.
[0073] For example, as further described herein, a continuous fine fiber layer acting as a surface loading layer prevents particles from passing through the filter media. Additionally, because the continuous fine fiber layer is very thin, its pressure drop does not increase as much as the pressure drop of a thicker media would. Furthermore, by combining the continuous fine fiber layer with an appropriate low solidity layer (i.e., an efficiency layer that acts as a depth loading layer), the life of the filter media can be extended. Additional Optional Configurations of Filter Media
[0074] As described above, the filter media includes a continuous fine fiber layer and an efficiency layer. However, in some embodiments, the filter media may include multiple continuous fine fiber layers and multiple efficiency layers. For example, in one embodiment, the filter media may include a first efficiency layer located on the upstream side of the filter media, a first continuous fine fiber layer located on the downstream side of the first efficiency layer, a second efficiency layer located on the downstream side of the first continuous fine fiber layer, and a second fine fiber layer located on the downstream side of the second efficiency layer. The support layer will typically be located on the downstream side of the most downstream continuous fine fiber layer. (See Figure 1B , left panel.)
[0075] For example, in another embodiment, the filter media includes a first efficiency layer located on the upstream side of the filter media, a first continuous fine fiber layer located on the downstream side of the first efficiency layer, a second efficiency layer located on the downstream side of the first continuous fine fiber layer, a second fine fiber layer located on the downstream side of the second efficiency layer, a third efficiency layer located on the downstream side of the first continuous fine fiber layer, and a third continuous fine fiber layer located on the downstream side of the third efficiency layer. The support layer will typically be located on the downstream side of the most downstream continuous fine fiber layer. (See Figure 1B , middle panel.)
[0076] In some embodiments, the filter media may include more than one efficiency layer located on the upstream side of the filter media, and a continuous fine fiber layer located on the downstream side of the efficiency layer. (See Figure 1B , right panel. ) Additional efficiency layers can be used, for example, to increase the capacity (and therefore life) of the filter media or to improve pressure drop. Such additional efficiency layers can also be referred to as load layers. An exemplary embodiment of a filter media is described and characterized in Example 6, which includes a support layer, a continuous fine fiber layer, an efficiency layer, and a second efficiency layer (or load layer). Characteristics of filter media
[0077] In some embodiments, the filter media described herein achieves improved efficiency without compromising pressure drop compared to media without one or more continuous fine fiber layers, i.e., the pressure drop of the filter media described herein is within 150%, within 100%, within 50%, within 20%, within 15%, or within 10% of the pressure drop of the filter media without one or more continuous fine fiber layers.
[0078] In some embodiments, the filter media described herein achieves improved efficiency without compromising pressure drop compared to media without one or more continuous fine fiber layers and without a support layer, i.e., the pressure drop of the filter media described herein is within 150%, within 100%, within 50%, within 20%, within 15%, or within 10% of the pressure drop of the filter media without one or more continuous fine fiber layers and without a support layer.
[0079] For example, in exemplary embodiments, the pressure drop of the filter media is in the range of 50% to 150% of the pressure drop observed with the efficiency layer(s) alone (i.e., the pressure drop of the filter media without the continuous fine fiber layer(s) and without the support layer).
[0080] In some embodiments, the filter media described herein achieves equivalent efficiency under circulating flow conditions compared to the efficiency of the media without the continuous fine fiber layer under steady flow conditions. Preferably, the efficiency is achieved without a significant pressure drop penalty. For example, the pressure drop is within 150%, within 100%, within 50%, within 20%, within 15%, or within 10% of the pressure drop of a filter media without one or more continuous fine fiber layers and without a support layer.
[0081] In some embodiments, the filter media described herein exhibit an overall beta-blocking capacity of at least 5, at least 7, or at least 10 under circulating flow conditions. 10μm The filter media may further exhibit a total beta of up to 50, up to 100, up to 200, up to 300, up to 500, up to 1000, up to 1500, or up to 2000. 10μm For example, the total β 10μm It can be in the range of 5 to 2000, in the range of 5 to 200, or in the range of 5 to 100.
[0082] Except when testing flat plate performance and running the test in single pass mode, ISO / CD 23369 Edition 1 can be used to evaluate cyclic flow conditions, and the test should be run at 25°C. The flow rate through the media can be cycled between 5mm / sec and 1.25mm / sec in a 10 second cycle. ISO 12103-1 intermediate test dust can be used as the particle. An upstream particle concentration of 10mg / L can be used. Continuous particle concentration measurements can be collected every 6 seconds. It can be useful to control the fluid conductivity to a range of 1000 picoSiemens / meter (pS / m) to 1500pS / m.
[0083] In some embodiments, one or more fibers of the filter media can be selected or treated to modify the electrostatic charge of the filter media. The charge typically includes a layer of positive or negative charge trapped at or near the polymer surface, or a charge cloud stored in the polymer bulk. The charge can also include polarized charges that are frozen when the dipoles of the molecules are aligned. Methods for subjecting materials to charge are well known to those skilled in the art. These methods include, for example, thermal methods, liquid contact methods, electron beam methods, plasma methods, and corona discharge methods. Average maximum pore size and mean flow pore size of the support layer and continuous fine fiber layer of the composite material
[0084] As described above, the filter medium includes a support layer and a continuous fine fiber layer. In some embodiments, the continuous fine fiber layer may include multiple continuous fine fiber layers. These support layers and one or more continuous fine fiber layers may form a composite material. The composite material includes at least one continuous fine fiber layer.
[0085] In some embodiments, the composite material average maximum pore size of the filter media is up to 20 μm, preferably up to 15 μm, and more preferably up to 14 μm. In some embodiments, the composite material maximum pore size of the filter media is at least 0.1 μm. As used herein, "composite material average maximum pore size" refers to the average maximum pore size of the composite material, which includes the support layer and any continuous fine fiber layer present in the layer adjacent to the support layer.
[0086] In some embodiments, the filter media has a composite mean flow pore size or P50 of up to 11 μm, preferably up to 9 μm, and more preferably up to 6 μm. In some embodiments, the filter media has a composite mean flow pore size or P50 of at least 0.1 μm. As used herein, "composite mean flow pore size" refers to the mean flow pore size of a composite material that includes a support layer and any continuous fine fiber layer present in a layer adjacent to the support layer.
[0087] In some embodiments, capillary flow porometry is preferably used to determine the composite mean maximum pore size and / or the composite mean flow pore size.
[0088] Without wishing to be bound by theory, it is believed that the composite average maximum pore size and the composite mean flow pore size depend on the fine fiber diameter, the relative amounts of small and large fine fibers, and the composite morphology (e.g., lamellar or hybrid), among other factors.
[0089] In some embodiments, the composite material can have a mean flow pore size similar to the mean flow pore size of the efficiency layer. For example, in some embodiments, the mean flow pore size (P50) of the composite material can be within 1%, 2%, 3%, 5%, 10%, 20%, 30%, 50%, 100%, or 200% of the mean flow pore size (P50) of an adjacent efficiency layer.
[0090] As described in Example 5, a composite average maximum pore size of a filter media may be associated with the filter media's ability to withstand a pressure drop of at least 20 psi during liquid filtration, indicating better filter performance than filter media that cannot withstand the same conditions.
[0091] Although the composite average maximum pore size of a filter media may be correlated to the filter media's ability to withstand at least a 20 psi pressure drop during liquid filtration, the composite average maximum pore size may sometimes provide inconsistent values if the media includes defects or unusually large maximum pores. Therefore, to better understand the pore size range and pore size distribution of the composite, additional values were also examined, as described below. P95 / P50 ratio of composite materials including support layer and continuous fine fiber layer
[0092] In some embodiments, the composite material formed from the support layer and the continuous fine fiber layer has a P95 / P50 ratio of up to 1.8, up to 1.9, or up to 2.
[0093] Although the pore size of the fine fiber layer controls most of the P95 / P50 ratio values of the composite, the interactions between the support layer and the continuous fine fiber layer also affect performance. Without wishing to be bound by theory, it is believed that these interactions make the pore size measurement of the composite more informative than the pore size measurement of the fine fiber layer alone.
[0094] The value of P50 reflects the pore diameter at which 50% of the fluid flows through a pore of that diameter or smaller. The value of P95 reflects the pore diameter at which 95% of the fluid flows through a pore of that diameter or smaller, with larger ratios of P95 / P50 generally reflecting a larger range of pore sizes and the presence of relatively larger pores.
[0095] Without wishing to be bound by theory, it is believed that composite materials having a P95 / P50 ratio greater than 2 will not provide adequate efficiency under circulating flow. Although a P95 / P50 ratio less than 2 provides an increase in pressure drop (due to increased solidity), since the continuous fine fiber layer is very thin (e.g., less than 50 μm), the corresponding pressure drop can be kept within acceptable limits.
[0096] In some embodiments, the composite material has a P95 / P50 ratio of at least 1. P95 / P50 ratio of the efficiency layer adjacent to the fine fiber layer
[0097] In some embodiments, the efficiency layer has a P95 / P50 ratio of at least 1.8, at least 1.9, or at least 2.
[0098] Without wishing to be bound by theory, it is believed that composites having a P95 / P50 ratio of less than 1.8 will exhibit a density within the range that would be expected to result in an undesirably high pressure drop. In addition, since the density increases with decreasing P95 / P50, the number of particles that may be captured by the composite is also reduced.
[0099] In some embodiments, the efficiency layer has a P95 / P50 ratio of up to 2.5, up to 3, up to 4, up to 5, up to 10, up to 15, or up to 20.
[0100] Without wishing to be bound by theory, a P95 / P50 ratio greater than 20 is expected to result in a media layer having larger pore sizes and thus too few pores of the size required to capture desired particle sizes (eg, particle sizes in the range of 1 μm to 100 μm).
[0101] For example, the efficiency layer has a P95 / P50 ratio in a range of 1.8-20, in a range of 2-10, or in a range of 2-5.
[0102] In some embodiments, it is preferred that the maximum value of the range including the P95 / P50 ratio of the composite material is equal to or lower than the minimum value of the range including the P95 / P50 ratio of the efficiency layer. In some embodiments, it is preferred that the P95 / P50 ratio of the composite material is equal to or lower than the P95 / P50 ratio of the efficiency layer.
[0103] For example, in an exemplary embodiment, the composite material has a P95 / P50 ratio of up to 1.8, while the efficiency layer has a P95 / P50 ratio of at least 1.8. In another exemplary embodiment, the composite material has a P95 / P50 ratio of up to 1.9, while the efficiency layer has a P95 / P50 ratio of at least 1.9. In yet another exemplary embodiment, the composite material has a P95 / P50 ratio of up to 2, while the efficiency layer has a P95 / P50 ratio of at least 2.
[0104] In some embodiments, it is preferred that the maximum value of the P95 / P50 ratio of the composite material is lower than the minimum value of the P95 / P50 ratio of the efficiency layer. For example, in an exemplary embodiment, the P95 / P50 ratio of the composite material is up to 1.8, while the P95 / P50 ratio of the efficiency layer is at least 2. In another exemplary embodiment, the P95 / P50 ratio of the composite material is up to 1.9, while the P95 / P50 ratio of the efficiency layer is at least 2.
[0105] For example, in some embodiments, the P95 / P50 ratio of the efficiency layer adjacent to the fine fiber layer can be up to 1.5 times, up to 2 times, up to 3 times, up to 4 times, up to 5 times, up to 6 times, up to 7 times, up to 8 times, up to 9 times, or up to 10 times greater than the P95 / P50 ratio of the composite material. Overlapping pore size distributions
[0106] In some embodiments, the pore size distribution of the efficiency layer overlaps the pore size distribution of the composite material (including the support layer and the fine fiber layer). If the filter media includes more than one efficiency layer, the pore size distribution of the efficiency layer adjacent to the fine fiber layer overlaps the pore size distribution of the composite material (including the support layer and the fine fiber layer). Without wishing to be bound by theory, it is believed that this overlap of pore size distribution increases the life of the filter.
[0107] When the pore size distribution of the efficiency layer and the pore size distribution of the composite material do not overlap (because the pore size of the composite material is smaller than that of the efficiency layer), the fine fiber layer captures particles of a size not captured by the efficiency layer. This capture in turn results in increased pressure drop and, therefore, shorter media life.
[0108] If the pore size of the efficiency layer and the pore size of the composite material do not overlap (due to the pore size of the composite material being larger than the pore size of the efficiency layer), then the fine fiber layer will not provide the desired efficiency improvement.
[0109] Similarly, if the pore size of the efficiency layer and the pore size of the composite material overlap across their entire ranges, the fine fiber layer may not provide the desired efficiency improvement.
[0110] Thus, in some embodiments, the P95 of the composite material preferably falls within the range provided by the P5 and P50 values of the efficiency layer.
[0111] As shown in Example 6, when the P95 of the composite material drops below the range provided by the P5 and P50 values of the efficiency layer adjacent to the fine fiber layer, the resulting pressure drop of the filter media is high (23.2 kPa), which is 150% greater than the pressure drop of the filter media that does not include the fine fiber layer and support layer.
[0112] Without wishing to be bound by theory, it is believed that the use of a composite material having a P95 that falls within the range provided by the P5 and P50 values of the adjacent efficiency layer allows the resulting filter media to take advantage of both the depth loading characteristics of the efficiency layer of the composite material and the surface loading characteristics of the continuous fine fiber layer. The efficiency loss during dynamic flow conditions observed when using a separate efficiency layer is not observed in the claimed media because of the higher compactness and lower pore size of the continuous fine fiber layer. However, the high pressure drop that would be experienced if a separate continuous fine fiber layer were used to achieve the desired efficiency is also avoided. Filter elements
[0113] In some embodiments, the filter media disclosed herein can be included in a filter element that includes a wire support.The wire support can be located downstream of the support layer.
[0114] In some embodiments, filter media (including, for example, filter media contained in a filter element) is pleated.
[0115] Exemplary filter elements include flat plate filters, cartridge filters, or other filter components. Examples of such filter elements are described in U.S. Patent Nos. 6,746,517; 6,673,136; 6,800,117; 6,875,256; 6,716,274; and 7,316,723. How to use
[0116] In some embodiments, the filter media of the present disclosure can be used to filter fluids, including, for example, fluid streams. Fluids include air, gas, and liquid. In some embodiments, the filter media of the present disclosure can be used to remove particles from a fluid stream.
[0117] In some embodiments, the filter media of the present disclosure can be used to filter air. In some embodiments, including when the filter media of the present disclosure is used to filter air, the filter media can be located upstream of other layers in a filter element.
[0118] In some embodiments, the filter media of the present disclosure may be used to filter gases. The gaseous stream may include, for example, air and / or industrial exhaust gases. In an exemplary embodiment, the filter media of the present disclosure may be used to filter blow-by gases from a diesel engine crankcase, which carry a large amount of entrained oil as an aerosol therein. In a further exemplary embodiment, the filter media of the present disclosure may be used in a gas turbine.
[0119] In some embodiments, the filter media of the present disclosure can be used to filter liquids. In some embodiments, including when the filter media of the present disclosure is used to filter liquids, the filter media can be located downstream of other layers in the filter element. Exemplary liquids can include, for example, aqueous liquids, hydraulic fluids, oils, fuels, lubricants, etc. Aqueous liquids can include natural and artificial streams, such as effluents, cooling water, process water, etc.
[0120] In some embodiments, the filter media of the present disclosure may be particularly well suited for use in applications where flow rates vary, including, for example, hydraulic applications. Variations in flow rate, including, for example, cyclic flow conditions, can have an adverse effect on filter media performance, and in particular, filter media efficiency, because variations in flow rate result in multiple opportunities for particles to pass through the media openings.
[0121] At the time of the present invention, the effect of varying flow rates on filter media performance is typically minimized by increasing the efficiency of the filter media, but increasing the efficiency of the filter media also results in a corresponding increase in pressure drop, i.e., an increase in the pressure required to force the fluid through the filter media. This increase in pressure drop results in more opportunities to bypass the filter (e.g., via a bypass valve), increased energy consumption, and shortened filter life. In contrast, the filter media of the present disclosure can achieve an increase in efficiency under circulating flow conditions without compromising pressure drop. Continuous fine fiber layer
[0122] The continuous fine fiber layer includes continuous fine fibers having a diameter of up to 10 microns (μm). In some embodiments, the continuous fine fiber layer includes a single layer. In some embodiments, the continuous fine fiber layer includes multiple continuous fine fiber layers. In some embodiments, when the continuous fine fiber layer includes multiple layers, the multiple layers may include fine fibers of different diameters. In some embodiments, when the continuous fine fiber layer includes multiple layers, one or more layers may include continuous fine fibers with different diameters within the layer. In some embodiments, when the continuous fine fiber layer includes multiple layers, each layer may include a different combination of continuous fine fibers with different diameters.
[0123] In some embodiments, the continuous fine fiber layer acts as a surface loading layer.
[0124] In some embodiments, the continuous fine fiber layer may include fibers having a diameter of at least 0.05 μm, at least 0.1 μm, at least 0.2 μm, at least 0.5 μm, or at least 1 μm.
[0125] In some embodiments, the continuous fine fiber layer may include fibers having a diameter of up to 1.5 μm, up to 2 μm, up to 3 μm, up to 4 μm, up to 5 μm, up to 6 μm, up to 7 μm, up to 8 μm, up to 9 μm, or up to 10 μm. For example, in exemplary embodiments, the continuous fine fiber layer includes fibers having a diameter in the range of 0.1 μm to 5 μm, in the range of 0.5 μm to 5 μm, in the range of 1 μm to 5 μm, or in the range of 1 μm to 2 μm. In some embodiments (including, for example, when the continuous fine fibers have an elliptical shape), the continuous fine fibers may preferably include fibers having a diameter in the range of 1 μm to 5 μm. In some embodiments (including, for example, when the continuous fine fibers do not include a mixture of fibers of different diameters), the continuous fine fibers may include fibers having a diameter in the range of 0.2 μm to 1.5 μm.
[0126] In some embodiments, the continuous fine fiber layer may include fibers having an elliptical (including circular) shape. For example, the cross-sectional major axis (width) of the fiber: cross-sectional minor axis (height) may be at least 2:1 (such as, for example, fettuccine) and up to 1:1 (such as, for example, spaghetti).
[0127] In some embodiments, the continuous fine fiber layer may preferably include fibers having a diameter ranging from 1 μm to 5 μm and a cross-sectional major axis (width): cross-sectional minor axis (height) ratio of at least 1.5:1 and up to 1:1.
[0128] In some embodiments, the solidity of the continuous fine fiber layer is at least 10%, at least 11%, at least 12%, at least 13%, at least 14%, at least 15%, at least 20%, or at least 25%. In some embodiments, the solidity of the continuous fine fiber layer is up to 15%, up to 20%, up to 25%, up to 30%, up to 35%, or up to 40%. In an exemplary embodiment, the solidity of the continuous fine fiber layer is in the range of 15% to 30%.
[0129] The density of the continuous fine fiber layer (c) can be calculated according to the dimensionless fiber resistance parameter F* 1.0 Calculated using the following equation: F* 1.0 =4.3548e 8.8822c . F* 1.0 It can be calculated according to the modified Kirsch-Fuchs equation, as further described in the examples. Mixed diameter fine fibers
[0130] In some embodiments, the continuous fine fiber layer may include a mixture of fibers of different diameters.
[0131] In some embodiments, the continuous fine fiber layer may include fibers of two different diameters. When the continuous fine fiber layer includes fibers of two different diameters, the ratio of the average diameter of fine fibers of "small" fiber diameter to the average diameter of fine fibers of "large" fiber diameter (small fine fiber diameter: large fine fiber diameter) may be at least 1:3 (i.e., the average fiber diameter of the large fine fibers is 3 times the average fiber diameter of the small fine fibers).
[0132] In some embodiments, the ratio of the average diameter of fibers of "small" fiber diameter to the average diameter of fibers of "large" fiber diameter (small fiber diameter: large fiber diameter) can be in the range of 1:3 to 1:6. For example, in an exemplary embodiment, the continuous fine fibers may include first fine fibers having an average diameter in the range of 0.2 μm to 0.3 μm, and second fine fibers having an average diameter in the range of 0.9 μm to 1.1 μm. In another example, the average diameter of the first fine fibers may be 0.25 μm, and the average diameter of the second fine fibers may be 1 μm. In yet another example, the average diameter of the first fine fibers may be 0.25 μm, and the average diameter of the second fine fibers may be 1.4 μm.
[0133] In embodiments where the continuous fine fiber layer includes a mixture of fibers of different diameters, the fibers of different diameters may be mixed or intermingled together within a single layer of the continuous fine fiber layer.
[0134] In embodiments where the continuous fine fiber layer includes a mixture of fibers of different diameters, the fibers of different diameters can form different strata in the continuous fine fiber layer. When the fibers of different diameters form different strata in the continuous fine fiber layer, larger fibers can be deposited on a support before depositing smaller fibers, thereby creating a gradient within the continuous fine fiber layer (including, for example, in terms of pore size and density). Additionally or alternatively, when the fibers of different diameters form different strata in the continuous fine fiber layer, larger fibers and smaller fibers can be deposited to form multiple layers with different characteristics. Exemplary embodiments of this construction are described in detail in the accompanying drawings. Figure 2A as well as Figures 2H to 2M Further exemplary embodiments of continuous fine fiber layers including a mixture of fibers of different diameters are provided in co-pending application entitled "FILTER MEDIALAYERS INCLUDING MIXED DIAMETER FINE FIBERS" filed on the same date as this application (Attorney Docket No. 0444.000110WO01).
[0135] In some embodiments, the average diameter of the "large" fine fibers is at least 0.6 μm, more preferably greater than 0.6 μm. In some embodiments, the average diameter of the "large" fine fibers is at least 0.7 μm, at least 0.8 μm, or at least 0.9 μm. In some embodiments, the average diameter of the "large" fine fibers is preferably at least 1 μm or greater than 1 μm. The average diameter of the "large" fine fibers can be up to 1.1 μm, up to 1.2 μm, up to 1.3 μm, up to 1.4 μm, up to 1.5 μm, up to 2 μm, up to 3 μm, up to 4 μm, up to 5 μm, or up to 10 μm. An exemplary image of a continuous fine fiber layer including large fine fibers deposited on a support layer is shown in FIG. Figure 2B Shown in.
[0136] In embodiments where the continuous fine fiber layer includes "large" fine fibers and "small" fine fibers, the average diameter of the large fine fibers may be at least three times the average fiber diameter of the small fine fibers. In such embodiments, the average diameter of the small fine fibers may be up to 0.3 μm, up to 0.4 μm, up to 0.5 μm, or up to 0.6 μm. In some embodiments, the average fiber diameter of the small fine fibers of the continuous fine fiber layer may be at least 0.2 μm.
[0137] In some embodiments, the diameter of the large fine fibers can be at least 0.2 μm, at least 0.3 μm, or at least 0.4 μm larger than the diameter of the small fine fibers. As described above, even when the average fiber diameter of the large fine fibers is 3 times the average fiber diameter of the small fine fibers, either or both of the large fine fibers and the small fine fibers can include fibers of different sizes that provide an average diameter. When the large fine fibers and the small fine fibers include, for example, a distribution of sizes, the diameter of the large fine fibers with the smallest diameter can be at least 0.2 μm, at least 0.3 μm, or at least 0.4 μm larger than the diameter of the small fine fibers with the largest diameter. In some such embodiments, the large fine fibers and the small fine fibers can form a bimodal distribution. In some embodiments, the diameter of the large fine fibers can be up to 1 μm, up to 2 μm, or up to 3 μm larger than the diameter of the small fine fibers.
[0138] In some embodiments where the continuous fine fiber layer includes "large" fine fibers and "small" fine fibers, the continuous fine fiber layer may include at least 0.5% and up to 20% large fine fibers, more preferably at least 1% and up to 10% large fine fibers, or even more preferably at least 5% and up to 7% large fine fibers. Additional ranges may also be useful, including, for example, at least 3% and up to 9% large fine fibers, or at least 4% and up to 8% large fine fibers. Without wishing to be bound by theory, it is believed that optimizing the proportion of large fine fibers in the second fine fiber layer provides support for the small fine fibers without disrupting the small fine fiber structure and resulting in a corresponding loss of efficiency.
[0139] In some embodiments, the continuous fine fiber layer may include "large" fine fibers and "small" fine fibers, and the continuous fine fiber layer may include multiple layers. In an exemplary embodiment, the continuous fine fiber layer includes: a first fine fiber layer, which includes large fine fibers; and a second fine fiber layer, which includes small fine fibers. In another exemplary embodiment, the continuous fine fiber layer includes: a first fine fiber layer, which includes large fine fibers; and a second fine fiber layer, which includes large fine fibers and small fine fibers. In some embodiments, the first fine fiber layer can be deposited on a support layer, and the second fine fiber layer is deposited on the first fine fiber layer. Properties of the continuous fine fiber layer
[0140] In some embodiments, the continuous fine fiber layer preferably has a narrow pore size distribution.
[0141] In some embodiments, the continuous fine fiber layer has a basis weight of at least 0.005 g / m 2 , at least 0.01g / m 2 , at least 0.05g / m 2 , at least 0.1g / m 2 , at least 0.5g / m 2 , at least 1g / m 2 , at least 1.5g / m 2 , at least 2g / m 2 or at least 2.5g / m 2 In some embodiments, the continuous fine fiber layer has a basis weight of up to 1.5 g / m 2 , up to 2g / m 2 , up to 2.5g / m 2 , up to 3g / m 2 , up to 3.5g / m 2 , up to 4g / m 2 , up to 4.5g / m 2 , up to 5g / m 2 , up to 10g / m 2 , up to 15g / m 2 , up to 20g / m 2 , up to 25g / m 2 , up to 50g / m 2 In an exemplary embodiment, the continuous fine fiber layer has a basis weight of at least 0.1 g / m 2 And up to 20g / m 2 In another exemplary embodiment, the continuous fine fiber layer has a basis weight of at least 0.1 g / m 2 And up to 1g / m 2 In a further exemplary embodiment, the continuous fine fiber layer has a basis weight of 0.43 g / m 2When fibers of different diameters are layered, the basis weight of the continuous fine fiber layers will be additive.
[0142] The basis weight of the fine fibers can be calculated from the mass of the fine fibers and the area of the scrim according to the following equation: Total basis weight of the fine fiber layer = (mass of the fine fibers) / (area of the scrim). The mass of the fine fibers can be calculated from the polymer used to make the fiber and the spinning conditions according to the following equation: Mass of fine fibers = (% w / v polymer in solution) x (pump rate) x (spinning time).
[0143] In some embodiments, the thickness of the continuous fine fiber layer is at least the average diameter of the largest fine fibers of the continuous fine fiber layer. In some embodiments, the thickness of the continuous fine fiber layer is at least 0.2 μm, at least 0.3 μm, at least 0.4 μm, at least 0.5 μm, at least 0.6 μm, at least 0.7 μm, at least 0.8 μm, at least 0.9 μm, or at least 1 μm.
[0144] In some embodiments, the thickness of the continuous fine fiber layer is the thickness of several fibers having the average diameter of the largest fine fibers of the continuous fine fiber layer. For example, the thickness of the continuous fine fiber layer is at least 2 μm, at least 3 μm, at least 4 μm, or at least 5 μm.
[0145] In some embodiments, the continuous fine fiber layer has a thickness of up to 5 μm, up to 10 μm, up to 30 μm, or up to 50 μm.
[0146] In some embodiments, scanning electron microscopy (SEM) can be used to measure the total thickness of the continuous fine fiber layer. For example, a sample comprising at least a continuous fine fiber layer and a support layer can be prepared for SEM by cross-cutting the sample while frozen (e.g., in liquid nitrogen). It can be useful to cross-cut the sample while the sample is oriented, wherein the support layer is cut before the fine fiber layer. It can be further useful to cross-cut the sample while the sample is immersed in liquid nitrogen. An exemplary magnification that can be used is 1000x. It can be useful to use software to help determine the sample thickness by allowing the fine fiber profile to be outlined and recolored in the SEM image. The recolored image can then be used to determine the maximum thickness of the fine fiber profile in the image. In some embodiments, the total thickness of the fine fiber layer can be determined by averaging at least five maximum thicknesses from five separate images of the same sample. Properties of the fibers in the continuous fine fiber layer
[0147] The continuous fine fiber layer includes fine fibers. These fine fibers include a fiber-forming polymer material. In some embodiments, the fine fibers can be made by spinning a separate fiber-forming polymer material. In some embodiments, the fine fibers can be made by spinning a fiber-forming polymer material combined with another substance.
[0148] Fine fiber technology that contemplates polymer materials mixed or blended with various other substances is disclosed in the following: U.S. Pat. No. 6,743,273 to Chung et al.; U.S. Pat. No. 6,924,028 to Chung et al.; U.S. Pat. No. 6,955,775 to Chung et al.; U.S. Pat. No. 7,070,640 to Chung et al.; U.S. Pat. No. 7,090,715 to Chung et al.; U.S. Pat. Publication No. 2003 / 0106294 to Chung et al.; U.S. Pat. No. 6,800,117 to Barris et al.; and U.S. Pat. No. 6,673,136 to Gillingham et al. Additionally, in U.S. Pat. No. 7,641,055 to Ferrer et al., a water-insoluble high strength polymer material is made by mixing or blending a polysulfone polymer with a polyvinylpyrrolidone polymer to produce a single-phase polymer alloy for electrospinning a fine fiber material.
[0149] The continuous fine fibers may include fibers made of any suitable polymer. In some embodiments, polyamides may be used as the polymer material of the continuous fine fibers. A useful class of polyamide condensation polymers is nylon materials. The term "nylon" is a common name for all long-chain synthetic polyamides. Typically, the nylon nomenclature includes a series of numbers, such as nylon-6,6, which indicates that the starting material is a C6 diamine and a C6 diacid (the first number indicates a C6 diamine, and the second number indicates a C6 dicarboxylic acid compound). Another nylon can be made by polycondensing ε-caprolactam in the presence of a small amount of water. This reaction forms nylon-6 (made of a cyclic lactam also known as ε-aminocaproic acid) as a linear polyamide. Further, nylon copolymers are also envisioned. Exemplary nylon materials include nylon-6, nylon-6,6, nylon-6,10, mixtures thereof, or copolymers.
[0150] Copolymers can be made by combining various diamine compounds, various diacid compounds, and various cyclic lactam structures in a reaction mixture, and then using randomly positioned monomer materials to form nylon in a polyamide structure. For example, nylon-6,6-6,10 material is a nylon made from hexamethylenediamine, and a blend of C6 and Cio diacids. Nylon-6-6,6-6,10 is made from ε-aminocaproic acid, hexamethylenediamine, and a blend of C6 and Cio diacids. 10 Nylons made by copolymerization of blends of diacid materials. As used herein, the term "copolymer" includes polymers made from two or more different monomers, and includes terpolymers and the like.
[0151] In some embodiments, polysulfones may be used as the polymer material of the continuous fine fibers. Exemplary polysulfones include polysulfone (PS), polyethersulfone (PES), and polyphenylsulfone (PPSF), and mixtures thereof.
[0152] In some embodiments, a polymer material including a cellulose derivative may be used as the polymer material of the continuous fine fibers. Examples of such polymers include ethyl cellulose, hydroxyethyl cellulose, cellulose acetate (including diacetate cellulose (DAC) and triacetate cellulose (TAC)), cellulose acetate butyrate, cellulose acetate propionate, cellulose acetate phthalate, and mixtures thereof.
[0153] In some embodiments, the polymer material of the continuous fine fibers may additionally or alternatively include polypropylene (PP), polyvinylpyrrolidone (PVP), poly(4-vinylpyridine) (P4VP), polyvinylidene fluoride (PVDF), or polytetrafluoroethylene (PTFE, also known as Teflon), or mixtures thereof.
[0154] In some embodiments, polymers cross-linked with resinous aldehydes may be used as the polymer material for the continuous fine fibers, as described, for example, in International Publication No. WO 2013 / 043987 A1.
[0155] In some embodiments, the solidity of the continuous fine fiber layer is greater than the solidity of one or more other layers in the filter media, including, for example, the support layer or the efficiency layer or both. Without wishing to be bound by theory, although layers having high solidity typically result in an increase in pressure drop, it is believed that providing a very thin continuous fine fiber layer helps provide efficiency improvements without the corresponding pressure drop that would typically be observed.
[0156] In some embodiments, the continuous fine fiber layer has a mean flow pore size similar to the mean flow pore size of the efficiency layer. In some embodiments, the continuous fine fiber layer has a pore size distribution that is narrower than the pore size distribution of the efficiency layer.
[0157] In some embodiments, fine fibers can be made by combining a fiber-forming polymer material and at least two reactive additives that are capable of reacting with each other (e.g., in a fiber-forming process or in a post-treatment process), as further described in International Patent Publication No. WO 2014 / 164130. The at least two reactive additives are optionally reactive with the fiber-forming polymer.
[0158] In some embodiments, fine fibers may be made by combining a fiber-forming polymer material and a resinous aldehyde composition (eg, melamine-formaldehyde resin).
[0159] In some embodiments, the resin-aldehyde composition includes a "polymer-reactive resin-aldehyde composition". The "polymer-reactive resin-aldehyde composition" includes alkoxy groups, as further described in U.S. Patent No. 9,587,328. In the final fiber, at least a portion of the polymer-reactive resin-aldehyde composition will participate in crosslinking the polymer, and optionally can participate in self-crosslinking. The fiber-forming polymer material also includes reactive groups. In this context, "reactive" means that the polymer includes one or more functional groups (e.g., active hydrogen groups) that can be used to make alkoxy crosslinks of the polymer-reactive resin-aldehyde composition of the fine fiber.
[0160] In some embodiments, the resinous aldehyde composition comprises a "polymer non-reactive resinous aldehyde composition". The polymer non-reactive resinous aldehyde composition comprises reactive groups for self-crosslinking, as further described in U.S. Pat. No. 9,435,056. In the final fiber, at least a portion of the polymer non-reactive resinous aldehyde composition will participate in self-crosslinking.
[0161] As used herein, "resin" or "resinous" refers to monomers, oligomers, and / or polymers that have the property of migrating to the surface of fine fibers during fiber formation. Herein, the term "resinous aldehyde composition" refers to the starting material as well as the material in the final fiber. Method for forming a continuous fine fiber layer
[0162] In another aspect, the present disclosure describes a method of making a continuous fine fiber layer.
[0163] The continuous fine fiber layer can be formed by any suitable method. For example, the fine fibers of the present disclosure can be made using various techniques, including electrospinning, force spinning, wet spinning, dry spinning, melt spinning, extrusion spinning, direct spinning, gel spinning, by using the island-in-the-sea method, etc.
[0164] In some embodiments, the components of the continuous fine fiber layer can be combined in solution or melt form. In certain embodiments, the fine fibers are electrospun from a solution or dispersion. For example, the polymeric material and the resinous aldehyde composition can be dispersed or dissolved in at least one common solvent or solvent blend suitable for electrospinning.
[0165] In some embodiments, the continuous fine fiber layer can be formed on a support layer. In some embodiments, the continuous fine fiber layer can be formed on an efficiency layer.
[0166] In some embodiments, when fibers of different diameters can form different layers in a continuous fine fiber layer, larger fibers can be deposited on a support before depositing smaller fibers. Depending on the number of layers, additionally or alternatively, smaller fibers can be deposited on a support before depositing larger fibers.
[0167] In some embodiments, when fibers of different diameters may form the same layer in a continuous fine fiber layer, the fibers may be formed simultaneously.
[0168] The fine fibers are collected on the support layer during formation, such as electrostatic or melt spinning, and are often heat treated after fiber production. Preferably, the continuous fine fiber layer is disposed on a first surface of a permeable coarse fiber medium layer (ie, support layer) as a fibrous layer.
[0169] One of ordinary skill in the art can select appropriate polymers and polymer concentrations, taking into account the desired size and other properties for the continuous fine fiber layer. For example, in some embodiments, the fibers will preferably be compatible with the fluids (e.g., hydraulic fluids, fuels, lubricants) that they are used to filter. A fiber is considered compatible with a fluid if it does not react with the fluid or any other components and additives therein and is insoluble in the fluid (such that the fine fiber structure is neither chemically nor physically damaged when merely in contact with the fluid). In an exemplary embodiment, the polymer solution includes solution 1, as described in the example. In an exemplary embodiment, the polymer solution includes solution 2, as described in the example.
[0170] In some embodiments, when fine fibers of different diameters are mixed, these fibers can be formed simultaneously. For example, when two (or more) fibers are formed by electrospinning, these fibers can be formed by co-spinning at the same time, including, for example, by using two (or more) syringes, wherein each syringe includes a different polymer solution. Additionally or alternatively, each syringe can use a different syringe pump feed rate. In some embodiments, when fine fibers of different diameters are mixed, these fibers can be formed by alternatingly forming fibers, but using very short (e.g., up to 10 seconds, up to 20 seconds, or up to 30 seconds) pulses of each polymer solution.
[0171] In some embodiments, when fibers of different diameters are layered, these fibers can be formed by alternately forming fibers. For example, when two (or more) fibers are formed by electrospinning, these fibers can be formed by alternatively spinning each fiber, including, for example, by using two (or more) syringes, wherein each syringe includes different polymer solutions. Additionally or alternatively, each syringe can use different syringe pump feed rates. In some embodiments, when fibers of different diameters are layered, these fibers can be formed by alternately forming fibers using pulses of at least 30 seconds of each polymer solution.
[0172] Any suitable method can be used to form a combination of small fine fiber layers and large fine fiber layers that can be used. Exemplary methods that can be used to form layered fiber structures include one or more of the methods of Group A5, Group B, Group D5, Group E, Group I5, or Group J of Table 1. Exemplary methods that can be used to form hybrid fiber structures include one or more of the methods of Group A6, Group D, Group D6, Group I, or Group L of Table 1. In some embodiments, a combination of layers including both layered fiber structures and hybrid fiber structures can be formed. Exemplary methods for forming such structures are described in the examples. Efficiency Layer
[0173] The efficiency layer is a nonwoven filter media.
[0174] In some embodiments, the efficiency layer preferably acts as a depth loading layer.
[0175] Exemplary nonwoven filter media include wet-laid resinless media, wet-laid resin-bonded glass media, meltblown media, wet-laid cellulosic media, and air-laid glass media.
[0176] Exemplary wet-laid resin-free media include Synteq XP with a 10 micron efficiency rating TM Synthetic liquid media (Duramax P164378, Donaldson Co., Minneapolis, MN), and Synteq XP with 5-micron efficiency rating TM Synthetic liquid medium (Duramax P165332, Donaldson Co., Minneapolis, MN).
[0177] Exemplary wet-laid resin-bonded glass media include: media in the Lydall LyPore series, such as LyPore XL Fluid Power 9104 (Lydall, Inc., Manchester, CT); media in the Ahlstrom Microglass series, such as MFPS1301 (Ahlstrom- Helsinki, Finland); and H&V hydraulic media, such as Grade 1313 (Hollingsworth & Vose, East Walpole, Mass.).
[0178] Exemplary meltblown media include media in the Lydall LyPore MB series, such as LyPore MB9031 (Lydall, Inc., Manchester, CT); and media in the H&V meltblown series, grade PF23040 (Hollingsworth & Vose, East Walpole, MA).
[0179] Exemplary wet-laid cellulose media include: media in the Ahlstrom fuel media series, such as grade 100P-68 (Ahlstrom- Helsinki, Finland); and media in the H&V fuel media series, such as grade FS6314 (Hollingsworth & Vose, East Walpole, Mass.).
[0180] Exemplary airlaid media include those found in air filtration media from Johns Manville, such as Evalith XLG-85 (Johns Manville, Denver, Colorado).
[0181] In some embodiments, the efficiency layer is preferably a wet-laid media.
[0182] In some embodiments, the efficiency layer comprises bicomponent fibers and efficiency fibers, wherein the efficiency fibers have a smaller diameter than the bicomponent fibers. In some embodiments, the efficiency layer may further comprise microfibrillated cellulose.
[0183] In some embodiments, the efficiency layer has a less solidity than the continuous fine fiber layer.
[0184] In some embodiments, the density of the efficiency layer is at least 3%, at least 4%, at least 5%, at least 6%, at least 7%, at least 8%, at least 9%, or at least 10%. In some embodiments, the density of the efficiency layer is up to 8%, up to 9%, up to 10%, up to 11%, up to 12%, up to 13%, up to 14%, or up to 15%. In exemplary embodiments, the density of the efficiency layer is in the range of 7% to 12%. In some embodiments, the density of the efficiency layer is calculated using the following equation: c=BW / ρZ, where BW is the basis weight, ρ is the density of the fiber, and Z is the thickness of the medium. If the efficiency layer includes different fibers, the mass ratio of these fibers can be used to determine the density (ρ). The basis weight can be measured according to TAPPI T410 om-08. The thickness can be measured according to TAPPI T411 om-15.
[0185] In some embodiments, the thickness of the efficiency layer is at least 0.05 mm, at least 0.1 mm, at least 0.2 mm, or at least 0.3 mm. In some embodiments, the thickness of the efficiency layer is up to 0.5 mm, up to 1 mm, up to 5 mm, up to 10 mm, up to 25 mm, or up to 50 mm. In some embodiments, the thickness of the efficiency layer is in the range of 0.2 mm to 50 mm. In some embodiments, the thickness of the efficiency layer is in the range of 0.2 mm to 1 mm. In some embodiments, the thickness of the efficiency layer is in the range of 0.2 mm to 0.5 mm. The thickness can be measured according to TAPPI T411 om-15.
[0186] As described above, in some embodiments, the continuous fine fiber layer has a mean flow pore size similar to the mean flow pore size of the efficiency layer. Without wishing to be bound by theory, it is believed that if the mean flow pore size of the continuous fine fiber layer is much smaller than the mean flow pore size of the efficiency layer, a larger proportion of particles will be captured by the continuous fine fiber layer, thereby reducing the filter life. On the other hand, if the mean flow pore size of the continuous fine fiber layer is much larger than the mean flow pore size of the efficiency layer, the efficiency layer must have a high density and the filter will again have a reduced life due to lower capacity.
[0187] It will be appreciated that the mean flow pore size may be selected based on the desired efficiency of the filter media and the size of the particles being filtered.
[0188] In exemplary embodiments, the mean flow pore size of the efficiency layer is at least 1 μm, at least 5 μm, at least 10 μm, at least 15 μm, or at least 20 μm. In exemplary embodiments, the mean flow pore size of the efficiency layer is up to 5 μm, up to 10 μm, up to 15 μm, up to 20 μm, up to 25 μm, up to 30 μm, or up to 35 μm. In specific exemplary embodiments, the efficiency layer fibers have a mean flow pore size range of 10 μm to 25 μm. In some embodiments, the mean flow pore size is preferably a mean flow pore size determined using capillary flow porometry, as described in the examples.
[0189] In some embodiments, the efficiency layer has a broader pore size distribution than the pore size distribution of the adjacent continuous fine fiber layer.
[0190] As described above, in some embodiments, the continuous fine fiber layer has a pore size distribution that is narrower than the pore size distribution of the adjacent efficiency layer.
[0191] In some embodiments, the resinous binder component is not necessary to obtain sufficient strength for the efficiency layer. In some embodiments, the resinous binder component is not included in the efficiency layer. Bicomponent Fibers
[0192] Bicomponent fibers may include any suitable bicomponent fibers or combinations of bicomponent fibers. The term "bicomponent fiber" means a fiber having: at least one thermoplastic binder polymer portion having a melting point; and a second thermoplastic structural polymer portion having a melting point different from and higher than the binder polymer portion. The physical configuration of these fibers is typically a "side-by-side" or "skin-core" structure. In a side-by-side structure, two thermoplastic polymer resins are typically extruded in a connected form in a side-by-side structure. The low melting point polymer acts as a binder, while the high melting point polymer acts as a structural material. In a skin-core structure, the core contains a higher structural fiber melting point, while the skin contains a lower bonding layer melting point. In some embodiments, the bicomponent fiber preferably has a skin-core structure.
[0193] The low melting point polymer of the bicomponent fibers can have a melting point such that during the thermoforming process the fibers are heated to a temperature such that the low melting point polymer can fuse and bond the fibers into a complete web. Typically, the high melting point polymer of the bicomponent fibers is a material that provides structural integrity to the web and does not melt either at the thermobonding temperature or at the use temperature.
[0194] For example, in one embodiment, the bicomponent fiber may include a low melting point polymer having a melting point of at least 100° C., at least 120° C., or at least 140° C. In some embodiments, the low melting point polymer has a melting point in the range of 140° C. to 160° C. The bicomponent fiber may further include a high melting point polymer having a melting point of at least 235° C. or at least 240° C. In some embodiments, the low melting point polymer has a melting point in the range of 240° C. to 260° C.
[0195] In another embodiment, the bicomponent fiber may include a low melting point polymer having a melting point of at least 50° C., at least 60° C., or at least 70° C. In some embodiments, the low melting point polymer has a melting point in the range of 70° C. to 115° C. The bicomponent fiber may further include a high melting point polymer having a melting point of at least 200° C., at least 220° C., or at least 240° C. In some embodiments, the high melting point polymer has a melting point in the range of 240° C. to 260° C.
[0196] Without wishing to be bound by theory, it is believed that while the relatively low melting point weight polymer of the bicomponent fibers melts under sheet, media or filter forming conditions to bond the bicomponent fibers and other fibers present in the sheet, media or filter manufacturing material into a mechanically stable sheet, media or filter, the high melting point polymer of the bicomponent fibers helps maintain the low density structure of the efficiency layer during the thermoforming process because the high melting point polymer does not melt and, therefore, holds the other fibers in the web separate.
[0197] In some embodiments, the efficiency layer can include a first bicomponent fiber and optionally a second bicomponent fiber. Including a second bicomponent fiber having different characteristics than the first bicomponent fiber can improve the ease of forming the fibers into a sheet, layer, and / or filter media.
[0198] For example, the first bicomponent fiber may include a low melting point polymer having a melting point of at least 100°C, at least 120°C, or at least 140°C. In some embodiments, the melting point of the low melting point polymer is in the range of 140°C to 160°C. The first bicomponent fiber may further include a high melting point polymer having a melting point of at least 235°C or at least 240°C. In some embodiments, the melting point of the low melting point polymer is in the range of 240°C to 260°C. The second bicomponent fiber may include a low melting point polymer having a melting point of at least 50°C, at least 60°C, or at least 70°C. In some embodiments, the melting point of the low melting point polymer is in the range of 70°C to 115°C. The second bicomponent fiber may further include a high melting point polymer having a melting point of at least 200°C, at least 220°C, or at least 240°C. In some embodiments, the melting point of the high melting point polymer is in the range of 240°C to 260°C.
[0199] The fiber diameter of the bicomponent fibers is typically in the range of 5 μm to 50 μm, often in the range of 10 μm to 20 μm. The length of the bicomponent fibers is typically in the range of 0.1 millimeters (mm) to 20 mm, often having a length of about 0.2 mm to about 15 mm.
[0200] Bicomponent fibers can be made of any suitable material, including, for example, various thermoplastic materials, including polyolefins (e.g., polyethylene, polypropylene, etc.); polyesters (e.g., polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.); nylons (e.g., nylon 6, nylon 6,6, nylon 6,12, etc.). Any thermoplastic that can have an appropriate melting point can be used in the bicomponent fiber, and a high melting point polymer can be used in the high melting point portion of the fiber. The bicomponent fiber can have, for example, a PET / PET or nylon 6 / nylon 6,6 structure, which has PET / components or nylons with different melting points.
[0201] Exemplary bicomponent fibers may include polyolefin / polyester (sheath / core) bicomponent fibers, whereby the polyolefin (e.g., polyethylene sheath) melts at a lower temperature than the core (e.g., polyester, or polyester / polyester, or nylon / nylon material). Typical thermoplastic polymers include: polyolefins, such as polyethylene, polypropylene, polybutylene, and copolymers thereof; polytetrafluoroethylene; polyesters, such as polyethylene terephthalate; vinyl acetates, such as polyvinyl acetate, polyvinyl chloride acetate; polyvinyl butyral; acrylic resins, such as polyacrylates, polymethacrylates, polymethyl methacrylates; polyamides, such as nylon; polyvinyl chloride, polyvinylidene chloride; polystyrene; polyvinyl alcohol; polyurethane; cellulosic resins, such as cellulose nitrate, cellulose acetate, cellulose acetate butyrate, ethyl cellulose, and the like; copolymers of any of the above materials, such as ethylene-vinyl acetate copolymers, ethylene-acrylic acid copolymers, styrene-butadiene block copolymers, Kraton rubber, and the like. Efficiency Fiber
[0202] The efficiency fibers can be made of any suitable material. For example, the efficiency fibers can include glass, metal, silica, polymer fibers, or other related fibers, or mixtures thereof. The efficiency fibers are typically monocomponent fibers (i.e., individual fibers are typically made of a single composition). The diameter of the efficiency fibers can be in the range of 0.1 μm to 50 μm, or more preferably in the range of 0.1 μm to 10 μm.
[0203] In some embodiments, the efficiency fibers include glass fibers.
[0204] In some embodiments, the efficiency fibers include chopped strands of a material other than glass. In some embodiments, the efficiency fibers preferably do not include glass fibers.
[0205] The chopped fibers may include, for example, hydrophilic, hydrophobic, oleophilic, or oleophobic fibers.
[0206] The chopped fibers may include one or more of a variety of materials including naturally occurring cotton, linen, wool, various cellulosic and protein natural fibers, or synthetic fibers including, for example, rayon, acrylic, aramid, nylon, polyolefins, polyesters. Microfibrillated cellulose
[0207] In some embodiments, the efficiency layer may include microfibrillated cellulose. For example, when the efficiency fibers are chopped fine fibers, the efficiency layer may include microfibrillated cellulose. In some embodiments (including when the chopped fine fibers include synthetic sample fibers), the efficiency layer may include microfibrillated cellulose.
[0208] Microfibrillated cellulose (MFC) herein refers to a material as defined by G. Chinga-Carrasco in Nano Research Letters (2011, 6:417): "MFC materials can be composed of: (1) nanofibrils, (2) fibril-like particles, (3) fiber fragments, and (4) fibers. This implies that MFC is not necessarily related to microfibrils, nanofibrils, or any other cellulose.
[0209] "Nanostructures are synonymous with microstructures. However, properly produced MFC materials contain as a major component nanostructures, i.e. nanofibrils." The diameters (or, for microfibrillated cellulose fibers, "transverse dimensions") of these components are reproduced in Table 1 of the same document and are as follows: (1) nanofibrils (less than 0.1 μm); (2) fibrillar particles (less than 1 μm); (3) fibers or fiber fragments (10 to 50 μm).
[0210] Furthermore, the term "microfibrillated cellulose" as used herein does not include dry-ground cellulose (also known as micronized cellulose or microfine cellulose), and does not include microcrystalline cellulose obtained by removing the amorphous portion by acid hydrolysis, as described in US Pat. No. 5,554,287.
[0211] In certain embodiments, the microfibrillated cellulose fibers used do not have a "tree structure" (as described in U.S. Patent Publication No. 2012 / 0043038), wherein the fibrillation process described causes the outer and inner segments of the fiber surface to partially break away from the main fiber structure and become fibrils that are attached to the main fiber structure by one segment. For example, such fibrils provide more structure on the fiber to attach to other fibers in the paper structure. For certain embodiments, this is undesirable.
[0212] Typically, microfibrillated cellulose fibers useful for filter media of the present disclosure have a transverse dimension (eg, width in 2 dimensions) of up to 4 μm. Typically, useful microfibrillated cellulose fibers have a transverse dimension of at least 700 nanometers (nm).
[0213] In certain embodiments, a majority (ie, greater than 50%) of the microfibrillated cellulose fibers have a transverse dimension of up to 4 microns. In certain embodiments, a majority (ie, greater than 50%) of the microfibrillated cellulose fibers have a transverse dimension of between 700 nm and 4 microns. Support layer
[0214] The support layer (also referred to herein as a substrate) of the filter media may include any material suitable for providing support to the continuous fine fiber layer during manufacture of the continuous fine fiber layer or during use of the continuous fine fiber layer, or both. The support layer may include or be made of any suitable porous material.
[0215] Typically, a fiber material will be used for the support layer. The fibers of the support layer can be made of natural fibers and / or synthetic fibers. Suitable fibers can include cellulose fibers, glass fibers, metal fibers, or synthetic polymer fibers, or a combination or mixture thereof.
[0216] In certain embodiments, the support layer comprises fibers having an average diameter of at least 5 microns or at least 10 microns. In some embodiments, the support layer may comprise fibers having an average diameter of up to 250 microns.
[0217] In some embodiments, the support layer is at least 0.005 inches (125 micrometers) thick, and often at least 0.01 inches (250 micrometers) thick. In some embodiments, the support layer is up to 0.03 inches (750 micrometers) thick.
[0218] In some embodiments, the support layer has a basis weight of at least 8 g / m 2 , at least 10g / m 2 , at least 15g / m 2 or at least 20g / m 2 In some embodiments, the support layer has a basis weight of up to 70 g / m 2 , up to 100g / m 2 or up to 150g / m 2 In an exemplary embodiment, the basis weight of the support layer is 8 g / m 2 Up to 150g / m 2 In another exemplary embodiment, the basis weight of the support layer is 15 g / m 2 Up to 100g / m 2 Basis weight can be measured according to TAPPI T410 om-08.
[0219] In some embodiments, the solidity of the support layer is at least 5%, at least 10%, at least 20%, at least 25%, at least 30%, or at least 40%. In some embodiments, the solidity of the support layer is up to 10%, up to 20%, up to 25%, up to 30%, up to 40%, or up to 50%. In an exemplary embodiment, the solidity of the support layer is in the range of 10% to 40%. In another exemplary embodiment, the solidity of the support layer is in the range of 20% to 30%. In some embodiments, the solidity of the support layer is calculated using the following equation: c=BW / ρZ, where BW is the basis weight, ρ is the density of the fiber, and Z is the thickness of the medium. If the efficiency layer includes different fibers, the mass ratio of these fibers can be used to determine the density (ρ). The basis weight can be measured according to TAPPI T410 om-08. The thickness can be measured according to TAPPI T411 om-15.
[0220] In some embodiments, the mean flow pore size of the support layer is at least 5 μm, at least 10 μm, at least 15 μm, at least 20 μm, or at least 25 μm. In some embodiments, the mean flow pore size of the support layer is up to 10 μm, up to 15 μm, up to 20 μm, up to 25 μm, up to 30 μm, up to 35 μm, up to 40 μm, up to 50 μm, up to 60 μm, up to 70 μm, up to 80 μm, or up to 90 μm. In an exemplary embodiment, the support layer has a mean flow pore size in the range of 10 μm to 25 μm. In some embodiments, the mean flow pore size is preferably a mean flow pore size determined using capillary flow porometry.
[0221] In some embodiments, the maximum pore size of the support layer is up to 10 μm, up to 15 μm, up to 20 μm, up to 25 μm, up to 30 μm, up to 35 μm, up to 40 μm, up to 50 μm, up to 60 μm, up to 70 μm, up to 80 μm, up to 90 μm, up to 100 μm, or up to 150 μm. In an exemplary embodiment, the maximum pore size of the support layer is up to 90 μm.
[0222] In some embodiments, the maximum pore size of a support layer (eg, nylon scrim) can be determined from capillary flow porometry.
[0223] In some embodiments, the support layer preferably comprises a uniform media structure, i.e., the characteristics of the media (including, for example, pore size, solidity, basis weight, or thickness, or a combination of those characteristics, or each of these characteristics of the media) are uniform across the length and width of the media. For example, in exemplary embodiments, the mean flow pore size does not vary by more than 30%, more preferably by no more than 25%, and even more preferably by no more than 15% across the length and width of the media.
[0224] Without wishing to be bound by theory, it is believed that the interaction between the fiber diameter of the fine fibers of the continuous fine fiber layer, the thickness of the one or more continuous fine fiber layers, and the maximum pore size of the support layer is critical to achieving a structurally robust and efficient media. For example, only higher basis weights (e.g., greater than 60 g / m 2) does not produce a structurally robust media because if the maximum pore size of the support layer exceeds a certain size (e.g., 90 μm), if the fine fiber diameter is below a certain size, and / or if the fine fiber thickness is small, the continuous fine fiber layer will become structurally compromised during filtration at a sufficiently high pressure drop. For example, when smaller fine fibers (e.g., having an average diameter of up to 500 nm) were used in the continuous fine fiber layer on a support layer having a maximum pore size of 88 μm, it was found that increasing the basis weight of the continuous fine fiber layer required unsustainable high pressures to pass fluid through the media; in contrast, decreasing the basis weight of the continuous fine fiber layer caused the layer to become structurally compromised during filtration. Although increasing the fiber size of at least one fiber of the continuous fine fiber layer deposited on a support layer having a maximum pore size of 88 μm (e.g., having an average diameter of at least 600 nm, more preferably at least 900 nm) reduces the efficiency of the media, increasing the fiber size also reduces the pressure drop and produces a structurally robust media that does not become structurally compromised during use.
[0225] The support layer can be formed by any suitable material. The example of suitable materials for the support layer includes spunbond, wet-laid, carded or melt-blown nonwoven materials or combinations thereof, including, for example, spunbond-meltblown-spunbond. The fiber can be in the form of a woven or nonwoven. The example of a synthetic nonwoven includes a polyester nonwoven, a nylon nonwoven, a polyolefin (e.g., polypropylene) nonwoven, a polycarbonate nonwoven or a blend or multicomponent nonwoven. A sheet-like support layer (e.g., cellulose, synthetic and / or glass or a combination net) is a typical example of a filter support layer. Other examples of suitable support layers include polyester or bicomponent polyester fibers or polypropylene / polyethylene terephthalate or polyethylene / polyethylene terephthalate bicomponent fibers in the form of spunbond.
[0226] In some embodiments, the support layer may preferably include polymer fibers. The one or more polymers of the polymer fibers may be selected so as to adhere to the polymer of the continuous fine fiber layer. In some embodiments, the polymer fibers may include nylon fibers or polyester fibers. For example, if the continuous fine fiber layer includes nylon fine fibers, the support layer may preferably include nylon.
[0227] In some embodiments, the support layer may preferably include spunbond fibers.Spunbond support layers, while exhibiting wide variation in pore size, are otherwise inexpensive and robust layers, which may make them particularly suitable for use as support layers in filter media.
[0228] In some embodiments, the support layer is a thin medium (eg, less than 0.5 mm) that exhibits high permeability; high tensile strength; and small, uniform pore size.
[0229] In an exemplary embodiment, the support layer comprises CEREX 23200 (Cerex Advanced Fabrics, Inc., Cantoment, FL). CEREX 23200 comprises nylon 6,6 having a thickness of 8.4 mils (0.21 mm) and a basis weight of 67.8 g / m 2 , density is 28%, and the permeability per density is 615.1.
[0230] As described in the Examples, using capillary flow porometry, CEREX 23200 was found to have an average maximum pore size of 66.4 μm ± 21.9 μm, a mean flow pore size of 51.4 μm ± 12.1 μm, and an average minimum pore size of 29.1 μm ± 9.7 μm.
[0231] The invention is defined in the claims. However, a non-exhaustive list of non-limiting exemplary aspects is provided below. Any one or more features of these aspects can be combined with any one or more features of another example, embodiment or aspect described herein. Exemplary Aspects
[0232] Aspect 1 is a filter medium comprising: a support layer; a continuous fine fiber layer having a thickness of up to 50 μm; and an efficiency layer; wherein the P95 / P50 ratio of the composite material comprising the support layer and the continuous fine fiber layer is up to 1.8, up to 1.9, or up to 2; wherein the P95 / P50 ratio of the efficiency layer is at least 1.8, at least 1.9, or at least 2; and wherein the P95 value of the composite material falls within the range provided by the P5 and P50 values of the efficiency layer.
[0233] Aspect 2 is the filter medium of aspect 1, wherein the composite material has a P95 / P50 ratio greater than 1.
[0234] Aspect 3 is the filter media of aspect 1 or 2, wherein the efficiency layer has a P95 / P50 ratio of up to 10, up to 15, or up to 20.
[0235] Aspect 4 is the filter medium of any of the preceding aspects, wherein the continuous fine fiber layer has a thickness of at least 2 μm.
[0236] Aspect 5 is the filter media of any of the preceding aspects, wherein the thickness of the continuous fine fiber layer is measured by scanning electron microscopy (SEM).
[0237] Aspect 6 is the filter media of any of the preceding aspects, wherein the continuous fine fiber layer is located between the efficiency layer and the support layer.
[0238] Aspect 7 is the filter media of any of the preceding aspects, wherein the efficiency layer is located on the upstream side of the filter media.
[0239] Aspect 8 is the filter media of any of the preceding aspects, wherein the filter media further comprises a second efficiency layer.
[0240] Aspect 9 is the filter media of aspect 8, wherein the second efficiency layer is adjacent to and upstream of the efficiency layer.
[0241] Aspect 10 is the filter media of any of the preceding aspects, wherein the efficiency layer comprises a wet-laid resinless media, a wet-laid resin-bonded glass media, a meltblown media, a wet-laid cellulose media, or an air-laid glass media.
[0242] Aspect 11 is the filter media of any of the preceding aspects, wherein the efficiency layer comprises a wet-laid media.
[0243] Aspect 12 is the filter media of any of the preceding aspects, wherein the efficiency layer comprises bicomponent fibers and efficiency fibers, wherein the efficiency fibers have a smaller diameter than the bicomponent fibers.
[0244] Aspect 13 is the filter media of aspect 12, wherein the efficiency fibers comprise glass fibers.
[0245] Aspect 14 is the filter media of aspect 12 or 13, wherein the efficiency fibers comprise chopped fine fibers.
[0246] Aspect 15 is the filter media of any of the preceding aspects, wherein the efficiency layer comprises microfibrillated cellulose fibers.
[0247] Aspect 16 is the filter media of any of the preceding aspects, wherein the continuous fine fiber layer comprises fibers having a diameter of up to 10 micrometers (μm).
[0248] Aspect 17 is the filter media of any of the preceding aspects, wherein the continuous fine fiber layer comprises fibers having a diameter of at least 1 micrometer (μm).
[0249] Aspect 18 is the filter media of any of the preceding aspects, wherein the continuous fine fiber layer comprises fibers having an elliptical shape.
[0250] Aspect 19 is the filter media of any of the preceding aspects, wherein the continuous fine fiber layer comprises a mixture of fibers of different diameters.
[0251] Aspect 20 is the filter media of aspect 19, wherein fibers of different diameters are intermixed within a single layer of the continuous fine fiber layer.
[0252] Aspect 21 is the filter medium of aspect 19 or 20, wherein fibers of different diameters form different layers in the continuous fine fiber layer.
[0253] Aspect 22 is the filter media of any of aspects 19 to 21, wherein the fibers of different diameters include large fine fibers and small fine fibers, wherein the average fiber diameter of the large fine fibers is at least 3 times the average fiber diameter of the small fine fibers.
[0254] Aspect 23 is the filter media of aspect 22, wherein the continuous fine fiber layer comprises: a first fine fiber layer comprising large fine fibers; and a second fine fiber layer comprising small fine fibers.
[0255] Aspect 24 is the filter medium of aspect 22 or 23, wherein the average diameter of the large fine fibers is at least 1 μm.
[0256] Aspect 25 is the filter media of any of aspects 22 to 24, wherein the diameter of the large fine fibers is at least 0.2 μm, at least 0.3 μm, or at least 0.4 μm greater than the diameter of the small fine fibers.
[0257] Aspect 26 is the filter media of any of the preceding aspects, wherein the continuous fine fibers comprise polyamide.
[0258] Aspect 27 is the filter media of any of the preceding aspects, wherein the support layer comprises a spunbond layer.
[0259] Aspect 28 is the filter medium of any of the preceding aspects, wherein the total β 10μm At least 5, at least 7 or at least 10 under circulating flow conditions.
[0260] Aspect 29 is the filter media of aspect 28, wherein, except when testing flat panel performance and running the test in single-pass mode, ISO / CD 23369 Edition 1 is used to evaluate circulating flow conditions and the test is run at 25°C; the flow rate through the media is cycled between 5 mm / sec and 1.25 mm / sec in a 10 second cycle; the ISO 12103-1 intermediate test dust provides an upstream particle concentration of 10 mg / L; continuous particle concentration measurements are collected every 6 seconds; and the fluid conductivity is controlled to a range of 1000 picoSiemens / meter (pS / m) to 1500 pS / m.
[0261] Aspect 30 is a filter element comprising the filter medium of any of the preceding aspects.
[0262] Aspect 31 is the filter element of aspect 30, wherein the wire support is located downstream of the support layer.
[0263] Aspect 32 is a method of filtering a fluid using the filter medium of aspects 1 to 29 or the filter element of aspect 30 or 31 .
[0264] Aspect 33 is the method of aspect 32, wherein the fluid comprises air, gas and liquid.
[0265] Aspect 34 is the method of aspect 32 or 33, wherein the fluid comprises hydraulic fluid, oil, fuel, or lubricant.
[0266] The present invention is illustrated by the following examples. It will be understood that the specific examples, materials, amounts, and procedures are to be interpreted broadly in accordance with the scope and spirit of the present invention as set forth herein. Example Preparation of polymer solutions
[0267] To prepare solution 1, a nylon copolymer resin (SVP 651 (Shakespeare Company, Columbia, South Carolina), a terpolymer with a number average molecular weight of 21,500 to 24,800, which includes 45% nylon-6, 20% nylon-6,6 and 25% nylon-6,10, see also Table 3) was dissolved in alcohol (ethanol, 190 degrees) and heated to 60°C to produce a 9% nylon solid solution. After cooling, melamine-formaldehyde resin (CYMEL 1133, Cytec Industries of West Paterson, New Jersey) was added to the solution to achieve a weight ratio of melamine-formaldehyde resin to nylon of 20:100 parts by weight. The melamine-formaldehyde resin acts as a crosslinking agent. Additionally, p-toluenesulfonic acid (7%, based on polymer solids) was added to the solution. The solution was stirred until homogeneous. Solution 1 was used to prepare 0.25 μm fibers.
[0268] Solution 2 was prepared as described for solution 1 except that a 17% nylon solids solution was used (and also resulted in a 20:100 parts by weight ratio of melamine-formaldehyde resin to nylon). Solution 2 was used to prepare 1 μm fibers.
[0269] The viscosity values of solutions 1 and 2 were measured at 25°C using a Brookfield LV DV-IPrime viscometer in combination with a Fisher Scientific Model 8005 temperature-controlled water bath and were found to be 30±5 cP and 300±5 cP, respectively.
[0270] To prepare solution 3, copolyamide (Griltex D 1523A, EMS-Griltech, Switzerland) was dissolved in a solvent mixture of ethanol, benzyl alcohol and water (ethanol: benzyl alcohol: water 16: 1: 1 by weight) and heated to 60°C to produce a 21% (w / w) solution. The viscosity of solution 3 was measured at 25°C using a Brookfield LV DV-IPrime viscometer in conjunction with a Fisher Scientific Model 8005 temperature-controlled water bath to be 473 ± 10 cP. Solution 3 was used to prepare 1.4 μm fibers. Sample preparation by hanging drop
[0271] The sample is prepared using a hanging drop apparatus (i.e., a syringe filled with a polymer solution). High voltage is applied to a needle attached to the syringe, and the polymer solution is pumped at a specified pump rate. As the droplet of polymer solution flows out of the needle, it forms a Taylor cone under the influence of the electrostatic field. At a sufficiently high voltage, a jet is ejected from the Taylor cone, which undergoes stretching, and fine fibers are formed and deposited on a medium attached to a rotating mandrel that acts as a collector.
[0272] The fibers were formed onto a support layer wrapped around a barrel (4 inches in diameter and rotating at 300 rpm) by electrospinning at a voltage of 24 kV and at a distance of 4 inches from one or more syringes that delivered one or more polymer solutions at a pump rate of 0.075 mL / min. After electrospinning, the formed fine fibers were heat treated at 140° C. for 10 minutes. Method 1:
[0273] The mixed fiber layer was deposited on a 0.2 mm thick spunbond nylon scrim with a basis weight of 70 g / m by co-spinning two different electrospinning precursor solutions (Solution 1 and Solution 2) from two different syringes. 2 and a solidity of 28% (Media Grade 23200, Cerex Advanced Fibers, Cantonment, Florida), delivered at the same pump rate (0.075 mL / min) from both syringes and for the same duration (5 minutes). Two control samples were prepared separately by spinning either Solution 1 or Solution 2 from a single syringe using the same pump rate and duration to produce a layer comprising only small fine fibers or large fine fibers, respectively.
[0274] All samples were subjected to post-synthesis treatment to improve robustness via cross-linking.After electrospinning, the formed fibers were heat treated at 140°C for 10 minutes. Method 2:
[0275] A series of mixed fiber layers were deposited on a 0.2 mm thick spunbond nylon scrim with a basis weight of 70 g / m by co-spinning solution 1 and solution 2 from two different syringes. 2 And the density is 28% (MediaGrade 23200, Cerex Advanced Fibers, Cantonment, Florida), and the two syringes are delivered at the same pump rate (0.075mL / minute) and for the same duration. Two control samples are prepared separately by co-spinning either solution 1 or solution 2 from two syringes using the same pump rate and duration to produce a layer comprising only small fine fibers or large fine fibers, respectively. In contrast to method 1, the basis weight between the control sample and the sample comprising the mixed fiber layer is more similar to that of the co-spinning control sample from two syringes (rather than one syringe) or solution 1 or solution 2.
[0276] All samples were subjected to post-synthesis treatment to improve robustness via cross-linking.After electrospinning, the formed fibers were heat treated at 140°C for 10 minutes. Method 3:
[0277] A series of fiber layers with fibers of different diameters were deposited on a 0.2 mm thick spunbond nylon scrim with a basis weight of 70 g / m by spinning alternately ("pulsing") from one of two syringes containing either Solution 1 or Solution 2. 2 and 28% solids (Media Grade 23200, Cerex Advanced Fibers, Cantonment, FL). Both syringes delivered at the same pump rate (0.075 mL / min) and alternated according to the timing sequence in Table 1.
[0278] All samples were subjected to post-synthesis treatment to improve robustness via cross-linking.After electrospinning, the formed fibers were heat treated at 140°C for 10 minutes. Method 4:
[0279] A series of hybrid fiber structures were deposited onto a 0.2 mm thick spunbond nylon scrim with a basis weight of 70 g / m using a two-step procedure. 2 The density is 28% (Media Grade 23200, Cerex Advanced Fibers, Cantonment, Florida).
[0280] In the first step, large fine fibers (equivalent to 0.43 g / m2 coverage) is deposited onto the scrim to act as an underlying support layer for subsequent fibers.
[0281] In the second step, a layer of mixed diameter fine fibers was deposited by alternately ("pulsing") spinning from either of two syringes containing Solution 1 or Solution 2 (for small and large fine fibers, respectively), both syringes delivering at the same pump rate (0.075 mL / min) and alternating according to the timing sequence in Table 1.
[0282] All samples (with a range from 0.65 to 0.86 g / m 2 The fibers were subjected to post-synthesis treatment to improve robustness via cross-linking. After electrospinning, the resulting fibers were heat treated at 140° C. for 10 minutes. Method 5
[0283] A series of structures (with different basis weight contributions from the small fine fiber component) were deposited onto a 0.2 mm thick spunbond nylon scrim with a basis weight of 70 g / m2 using a two-step procedure. 2 The density is 28% (Media Grade 23200, Cerex Advanced Fibers, Cantonment, Florida).
[0284] In the first step, large fine fibers (equivalent to 0.43 g / m 2 coverage) is deposited onto the scrim to act as an underlying support layer for subsequent fibers.
[0285] In the second step, a fine fiber layer was deposited by delivering Solution 1 at a pump rate of 0.075 mL / min. The basis weight of the fine fiber layer was 0.09 g / m 2 , 0.10g / m 2 , 0.22g / m 2 , 0.31g / m 2 , 0.45g / m 2 or 0.56g / m 2 , and were achieved by using an electrospinning duration of up to 48 seconds, 60 seconds, 120 seconds, 168 seconds, 240 seconds or 300 seconds, respectively. After electrospinning, the formed fibers were heat treated at 140° C. for 10 minutes. Table 1. Pulsed electrospinning sequence
[0286] *The proportion of larger fine fibers (based on fiber count) was estimated based on the diameters of small fine fibers (Solution 1) and large fine fibers (Solution 2), the % solids in the precursor spinning solution, and the syringe pump feed rate and spinning time, as described in the Fiber Proportion Calculation section below. Method 6
[0287] A series of media samples were made that included multiple layers of fine fibers of various sizes. The samples included a base layer of large fine fibers, followed by a layer of small fine fibers, and a top layer of large fine fibers (large / small / large, or L / S / L). Alternatively, the samples included a base layer of large fine fibers, followed by a layer of small fine fibers, then a layer of mixed small and large fine fibers, and a top layer of large fine fibers (large / small / mixed / large, or L / S / mixed / L).
[0288] The large fine fibers (equivalent to 0.43 g / m 2 Without wishing to be bound by theory, it is believed that the large fine fibers act as an underlying support layer for subsequent fiber layers. Next, a second layer of small fine fibers (equivalent to 0.22 g / m 2) was deposited by spinning Solution 1 for 2 minutes. 2 Coverage). If included, an intermediate (mixed) layer comprising both small and large fines was added by spinning alternately ("pulsing") from syringes containing either Solution 1 or Solution 2 (for small and large fines, respectively) according to the timing sequence in Table 1. Finally, a top large fine fiber layer (equivalent to 0.43 g / m 2 All solutions were delivered at a pump rate of 0.075 mL / min.
[0289] All samples (with a range from 1.31 to 1.52 g / m 2 The fibers were subjected to post-synthesis treatment to improve robustness via cross-linking. After electrospinning, the resulting fibers were heat treated at 140° C. for 10 minutes. Method 7
[0290] A series of media samples were also prepared that included a base layer of large fines and a mixed layer of small and large fines.
[0291] First, a first fine fiber layer (equivalent to 0.43 g / m 2 Coverage) was deposited on a 0.2 mm thick spunbond nylon scrim with a basis weight of 70 g / m 2and a solidity of 28% (Media Grade 23200, Cerex Advanced Fibers, Cantonment, FL). Next, a second fine fiber layer comprising intermixed small and large fine fibers was deposited by co-spinning two different electrospinning precursor solutions (Solution 1 and Solution 2) from two different syringes, both delivering at the same pump rate (0.075 mL / min) and for the same duration (either 2.5 minutes or 4.5 minutes).
[0292] All samples were subjected to post-synthesis treatment to improve robustness via cross-linking.After electrospinning, the formed fibers were heat treated at 140°C for 10 minutes. Method 8A
[0293] A single-sized fiber structure (nominal fiber diameter of 1.4 μm, basis weight of 0.67 g / m) was prepared from a polymer solution (21% w / w Griltex D 1523A (EMS-Griltech AG, Switzerland) in a solvent mixture of 16:1:1 by weight ethanol:benzyl alcohol:water) delivered at a pump rate of 0.075 mL / min via spinning at a needle-to-collector distance of 4 inches for 2.5 minutes at a 24 kV bias (Solution 3). 2 Coverage) was deposited on a 0.2 mm thick spunbond nylon scrim with a basis weight of 70 g / m 2 The density is 28% (Media Grade 23200, Cerex Advanced Fibers, Cantonment, Florida). Method 8B
[0294] A single sized fiber structure (nominal fiber diameter of 1 μm, basis weight of 2.59 g / m) was spun from a polymer solution (17% w / w SVP 651 (see Table 3) in ethanol) delivered at a pump rate of 0.075 mL / min (Solution 2) via spinning at a needle to collector distance of 4 inches for 12 minutes at a 24 kV bias. 2 Coverage) was deposited on a 0.2 mm thick spunbond nylon scrim with a basis weight of 70 g / m 2 The density is 28% (Media Grade 23200, Cerex Advanced Fibers, Cantonment, Florida). Method 8C
[0295] A single-sized fiber structure (nominal fiber diameter of 1.4 μm, basis weight of 4.02 g / m) was prepared from a polymer solution (21% w / w Griltex D 1523A (EMS-Griltech, Switzerland) in a solvent mixture of 16:1:1 by weight ethanol:benzyl alcohol:water) delivered at a pump rate of 0.075 mL / min via spinning at a needle-to-collector distance of 4 inches for 15 minutes at a 24 kV bias (Solution 3). 2 coverage) deposited onto a nylon scrim (Cerex, 70 g / m 2 )superior. Method 9:
[0296] Large fine fibers (equivalent to 0.54 g / m 2 coverage) is deposited onto the scrim.
[0297] Next, a second layer of fine fibers (equivalent to 0.22 g / m 2) was deposited by spinning Solution 1 at a 24 kV bias for 2 minutes at a needle to collector distance of 4 inches. 2 coverage).
[0298] Next, a third large fine fiber layer (equivalent to 0.54 g / m 2) was deposited by spinning Solution 3 at 24 kV bias for 2 minutes with a needle to collector distance of 4 inches. 2 coverage).
[0299] Finally, a top large fine fiber layer (equivalent to 0.54 g / m 2) was deposited by spinning Solution 3 at 24 kV bias for 2 minutes with a needle to collector distance of 4 inches. 2 coverage). Preparation of dielectric hand sheets
[0300] Handsheets were prepared by weighing the component fibers to achieve the desired basis weight target when formed into 30 cm x 30 cm sheets. A FORMAX 12" x 12" stainless steel sheet mold (Cat. No. G-100, Adirondack Machine Corporation, Hudson Falls, NY) was used as a handsheet former and prepared by placing a uniform nonwoven scrim layer with a pore size less than 100 μm at the bottom of the former (no removable forming wire was used). The former was then filled to nearly full with cold tap water, but with room to add an additional 1.5 L of water. 1 mL of Tide HE laundry soap (Procter & Gamble, Cincinnati, Ohio) was added to the water in the handsheet former. To prepare the fibers, 1 L of cold tap water was added to a Vitamix blender along with 200 mL of a 5% aqueous acetic acid solution. The weighed fibers were added to the blender and mixed at a medium to low speed for 180 seconds. The contents of the blender are then added to the handsheet former, and the contents of the handsheet former are mixed to ensure that the fibers are evenly distributed. Water is drained from the bottom of the handsheet former, allowing the fibers to form a sheet when collected on the nonwoven scrim. Vacuum suction is used on the line side to remove water from the sheet, and the handsheet (still on the scrim) is dried on a single-sided hot plate flash dryer (135-type flash dryer, Emerson Apparatus, Gorham, Maine) at 120°C for 10 minutes. The sheet (from the scrim) is removed and allowed to cool to ambient conditions before use. Medium Characterization Steady flow condition testing
[0301] Beta ratios were evaluated using ISO 16889:2008 (Hydraulic Fluid Power—Filters—Multi-pass method for evaluating the filtration performance of filter elements) under steady flow conditions, except when testing flat plate performance (the test was run in single-pass mode rather than the multi-pass mode required by the test standard). The test was run at 25°C rather than 40°C as required by the test standard. The flow rate through the media was 5 mm / sec. An ISO 12103-1 intermediate test dust (Powder Technology, Inc., Arden Hills, Minnesota) was used to provide an upstream particle concentration of 10 mg / L. Continuous particle concentration measurements were collected every 6 seconds. Circulation flow condition test
[0302] ISO / CD 23369 Edition 1 (Hydraulic Fluid Power - Multi-pass Method for Evaluating Filter Performance of Filter Elements under Cyclic Flow Conditions) was used to evaluate the beta ratio under cyclic flow conditions, except when testing flat plate performance (the test was run in single-pass mode instead of the multi-pass mode required by the test standard). The test was run at 25°C instead of 40°C as required by the test standard. The flow rate through the media was cycled between 5 mm / sec and 1.25 mm / sec in a 10 second cycle (approximately 5 seconds at each speed). An upstream particle concentration of 10 mg / L was provided using ISO 12103-1 intermediate test dust (Powder Technology Co., Ltd., Arden Hills, Minnesota). Continuous particle concentration measurements were collected every 6 seconds. The fluid conductivity was controlled to a range of 1000 to 1500 pico-Siemens / meter (pS / m). Calibration of particle counters
[0303] Particle counters are calibrated for use in ISO test procedures according to ISO 11171:2016 (Hydraulic fluid power—Calibration of automatic particle counters for liquids). Pressure Drop
[0304] The pressure drop was measured as described in ISO 3968:2017 using the test conditions shown in Table 2. Table 2 - Pressure drop test conditions fluid MIL5606 hydraulic oil Medium area <![CDATA[0.0507m 2 ]]> Fluid Viscosity 22 centistokes (cSt) Fluid temperature 25℃ Scanning electron microscopy (SEM)
[0305] Samples were prepared for top-down SEM imaging by sputter coating the surface with a mixture of gold and palladium, including a mixture of Au:Pd of 60:40. Typically, 5 kV or 10 kV accelerating voltage was used, and images were collected at x500, x1000, and x2500 magnifications using a secondary electron detector or a backscattered electron detector.
[0306] The sample was prepared for cross-sectional SEM imaging by the following steps: a 3 mm x 20 mm sample including fine fibers on a support layer was prepared, the sample fine fibers were placed face down in a weighing tank on a hard surface; the tank was filled with liquid nitrogen to immerse the sample. After at least 30 seconds, the sample was cut using a razor blade (while still immersed in liquid nitrogen) to expose the cross section. After the cut and an additional 10 to 20 seconds, the sample was removed from the liquid nitrogen and mounted to the SEM imaging piece. The sample was then sputter coated with 60:40 Au:Pd. Typically, a 5 kV accelerating voltage was used, and images were collected at x1000 magnification using a secondary electron detector. Fiber diameter
[0307] Fiber diameter sizing by scanning electron microscopy (SEM) was performed by imaging the fibers via a top-down SEM and measuring the fiber diameter (or other dimensions of interest) in the resulting micrographs. Fiber sizing was performed using image processing software such as ImageJ (FIJI Is Just ImageJ (FIJI), an updated version of ImageJ) and / or WekaSegmentation (ImageJ plugin). The diameter of the fiber was measured in at least 30 locations in the sample. Thickness of fine fiber layer
[0308] The thickness of the fine fiber sample was measured by scanning electron microscopy (SEM) via cross-sectional analysis of the SEM, prepared as described above. The thickness of the fine fiber layer was determined in at least 5 images from different parts of the sample using FIJI. Specifically, the top and bottom of the fine fiber layer were marked using the polygon tool, the area outside the selected fine fiber section was cleared, the area of the selected fine fiber section was recolored white using the threshold level tool to compensate for the fibers on the boundary of the selected section, and the maximum thickness in the image was measured and recorded. Five of these maximum values were rounded to the nearest tenth of a micron, and then they were averaged to provide the thickness of the fine fiber sample. Calculation of fiber ratio based on spinning time
[0309] The relative amounts of small and large fibers (based on total fiber count) are determined using the following equation:
[0310] Where D L and D S are the diameters of the large and small fibrils, respectively; and V L and V S are the volumes of the polymer including large and small fibers, respectively. The volume V of small or large fibers is calculated according to the following formula:
[0311] Where p is the density of the polymer including small fibrils or large fibrils, and % w / v refers to the solids content of the polymer solution on a mass / volume basis. Fiber ratio calculation based on microscopy
[0312] Sample images are obtained via SEM at appropriate magnifications (e.g., 500x, 1000x, or 2500x). The presence of one or more fiber populations is determined by counting all fibers within the image, followed by classification into small and large fibers based on group diameters within a 25% variation. Fiber size is measured using image processing software such as ImageJ. The proportion of small fibers is calculated by taking the ratio of the number of small fibers to the total number of fibers (both small and large fibers) within the image. Density
[0313] The solidity (c) of a nonwoven layer (including, for example, a non-fine fiber layer or a composite material including a fine fiber layer and a non-fine fiber layer) is calculated using the following equation: c=BW / ρZ
[0314] Where BW is the basis weight, p is the density of the fibers, and Z is the thickness of the media. If the nonwoven layer includes different fibers, the mass ratio of these fibers can be used to determine the density (p).
[0315] Thickness was measured according to TAPPI T411 om-15, entitled "Thickness (caliper) of paper, paperboard, and combined board", and a foot pressure of 1.5 psi was used. Basis weight was measured using TAPPI T410 om-08.
[0316] Since it is difficult to measure the thickness of the fine fiber layer, the compactness of the fine fiber layer is calculated using an adapted version of the Kirsch-Fuchs equation (see Kirsch et al., "Studies on Fibrous Aerosol Filters-III Diffusional Deposition of Aerosol in Fibrous Filters," Ann. Occup. Hyg., 1968; 11: 299-304) using experimentally measured pressure drop values. The pressure drop (ΔP or dP) was determined using a FHAST station as described below in the liquid filtration performance test section.
[0317] First, the dimensionless fiber resistance parameter F* is calculated according to the following modified Kirsch-Fuchs equation: 1.0 :
[0318] Where BW is the basis weight, ρ is the density of the fiber, μ is the viscosity of the liquid (for pressure drop testing), U ∞ is the velocity of the liquid through the medium during the pressure drop test, and D f is the effective fiber diameter. ΔP was determined based on the FHAST station as described below in the liquid filtration performance testing section.
[0319] Secondly, according to F*, we use the following equation 1.0 The density (c) is calculated as: F* 1.0 =4.3548e 8.8822c
[0320] For mixed fiber media, the effective fiber diameter accounts for the relative amounts of small and large fibers and is calculated according to the following equation:
[0321] where r eff is the effective fiber radius, r i is the radius of fiber i, and l i is the fraction or relative amount of fiber i. Effective fiber diameter = 2r eff .
[0322] The basis weight of the fine fiber layer or layers is calculated as follows: Total basis weight of fine fiber layer = (mass of fine fibers) / (area of scrim)
[0323] The mass of the fine fibers is calculated as follows: Mass of fine fibers = (% w / v polymer in solution) x (pump rate) x (spinning time)
[0324] When the method of making the fine fibers is unknown, the mass of the fine fibers can be calculated after separating the fine fibers from the scrim or support (e.g., by peeling or delamination) as follows:
[0325] Mass of fine fibers = (total mass of media sample) - (mass of bare scrim or support) Capillary flow porometry (pore size measurement)
[0326] Pore size measurements were performed by capillary flow porometry using a continuous pressure scan on a Porometer 3G (Quanachrome Instruments, Boynton Beach, CA). Flow Porosity Measurement Method A
[0327] The method uses Porofil wetting solution as the wetting fluid (Quantachrome Instruments, Anton Paar, Boynton Beach, FL) and tests the sample in both wet and dry states (wet then dry). The 25 mm diameter sample is subjected to a continuous pressure sweep from 0.0256 bar to 1.275 bar to determine the pore size in the range of 1 μm to 100 μm in diameter. Flow Porosity Measurement Method B
[0328] The method uses silicone oil with a surface tension of 20.1 dynes / cm and a wetting contact angle of 0, and the sample is tested in both wet and dry states (dry first, then wet). The sample with a diameter of 6 mm is subjected to a continuous pressure scan selected to measure most of the cumulative pore size distribution in the range of 2% to 98%.
[0329] For both methods, the samples were tested from low pressure to high pressure in both wet and dry states. The airflow and sample pressure from the saturated portion of the test are generally referred to as the wet curve. For both the dry and wet curves, 256 data points were collected across the scan range of pressure. Data points were collected throughout the scan at a rate of approximately 17 data points per minute. The tests were performed at ambient conditions (e.g., 20°C to 25°C). No empirical tortuosity factors and / or shape factors were applied to adjust the pore size diameter definition.
[0330] The flow porosimetry test procedure collects a set of pressure (typically plotted on the x-axis) and airflow (typically plotted on the y-axis) data for a dry sample, and a set of pressure and airflow data for a saturated (wet) sample. These two sets of data are commonly referred to as the dry curve and the wet curve. That is: Dry curve = V 干 = Air flow through the dry sample as a function of pressure Wet curve = V 湿 = Air flow through a saturated sample as a function of pressure
[0331] Based on capillary theory, the pressure (ΔP) at both ends of the sample can be converted into the pore diameter (d) using the Young-Laplace formula.
[0332] in, γ = surface tension of the fluid θ = fluid contact angle d = pore diameter ΔP = pressure at both ends of the sample
[0333] This conversion allows the definition of dry and wet curves as a function of pore diameter. That is: Dry curve = V' 干 = Air flow through the dry sample as a function of diameter Wet curve = V' 湿 = Airflow through a saturated sample as a function of diameter
[0334] The cumulative flow pore size distribution (Q) is defined as the ratio of the wet curve to the dry curve as a function of pore diameter.
[0335] The cumulative distribution can be expressed as an increasing cumulative distribution from 0% to 100%, or as a decreasing cumulative distribution from 100% to 0%. The pore size in this document is defined based on the increasing cumulative flow pore size distribution. Where, Increasing cumulative flow pore distribution = 1-Q(d)
[0336] To better identify points along this curve, this document defines various values of P(x%) equal to the corresponding pore diameter (d). P(x%)=d, where x%=1-Q(d)
[0337] Examples include, but are not limited to, the following: P5 is the pore diameter at which the cumulative flow pore distribution is 5%. P10 is the pore diameter at which the cumulative flow pore distribution is 10%. P50 is the pore diameter at which the cumulative flow rate of the pore distribution is 50%. P90 is the pore diameter at which the cumulative flow pore distribution is 90%. P95 is the pore diameter at which the cumulative flow pore distribution is 95%.
[0338] Where the maximum pore size is reported, the maximum pore size is determined by detecting the bubble point using the automatic bubble point (BP Auto Tolerance) method using a Porometer 3G (Quanachrome Instruments, Boynton Beach, California). According to this method, the bubble point is found after the fluid begins to pass through the sample and three consecutive measurements increase by at least 1%. The bubble point is the value at the beginning of this sequence of three points. Air filtration performance
[0339] Air filtration performance was assessed using a high efficiency flat plate (HEFS) TSI automated filter tester (Model 8127, Test Stand (TSI Incorporated, Shoreview, Minn.)) to measure particle capture efficiency using 0.3 μm oil (bis(2-ethylhexyl) sebacate, Sigma-Aldrich) droplets (aerosol) at a flow rate of 14.7 liters / minute (L / min) to challenge a 4-inch diameter media sample. TSI's CertiTest Model 8127 automated filter tester is designed to test filters, respirator cartridges, and filter media to the latest U.S. government and industry-wide specifications and meets the standards of 42 CFR §84 (June 8, 1995). Liquid filtration performance test
[0340] Liquid filtration performance was assessed using a flat-bed, high-accuracy, single-pass, two-fluid (FHAST) stage with the following features: Flow rate control: 57 mL / min to 580 mL / min with ±2% error; Temperature control: 25°C to 40°C with ±0.25°C error; dP measurement: 0 psi to 25 psi with ±0.065% error; Particle size: 1.7 μm to 20 μm; Maximum particle concentration: 1,000,000 / mL; Dilution capability: 5:1 to 100:1. The FHAST stage was used in static mode using an ISO intermediate test dust (10 milligrams per liter (mg / L) in hydraulic fluid and a flow rate of 0.347 L / min) according to ISO 11171:2016 to challenge a 2-inch diameter media sample. Media dP and efficiency values for specific contaminant particle sizes (measured using a commercially available particle counter, specifically a PAMAS 4132 particle counting system for liquids calibrated with ISO intermediate test dust in accordance with ISO 11171:2016, Hydraulic fluid power - Calibration of automatic particle counters for liquids) were collected at regular intervals (approximately every 7 seconds) throughout the duration of the test, with the test terminated when a preset maximum media dP of 20 psi was reached (measured using two test media dP sensors: (A) 0 psi to 5 psi, ±0.025% accuracy differential pressure transducer; high accuracy, low range dP sensor and (B) 0 psi to 25 psi, ±0.065% accuracy differential pressure transducer; low accuracy, high range dP sensor).
[0341] Beta ratios were evaluated using ISO 16889:2008 (Hydraulic Fluid Power—Filters—Multi-pass method for evaluating the filtration performance of filter elements) under steady flow conditions (347 mL / min through a 2-inch diameter media sample), except when testing flat plate performance (the test was run in single-pass mode rather than the multi-pass mode required by the test standard). The hydraulic fluid (Mobil Aero HF, MIL-PRF-5606) was saturated with ISO 12103-1A3 intermediate test dust (Inc., Arden Hills, MN) at a concentration of 10 mg / L. The instantaneous beta values were recorded every 7 seconds throughout the duration of the test. The test was terminated when an endpoint dP of 20 psi was reached. Quality Factor
[0342] The quality factor is a measure of the performance of the filter media and its ability to provide a certain degree of clarity of the fluid using the least amount of energy. Larger quality factor values are generally better than smaller values.
[0343] The figure of merit (FOM) value is calculated from the fractional penetration (P, the ratio of upstream counts to downstream counts), pressure drop (dP, inches H2O), and headwind velocity (u, fpm): FOM=(-log 10 P) / (dP / u)
[0344] Fractional penetration (P), pressure drop (dP) and headwind velocity (u) were measured using a HEFS TSI automatic filter tester (Model 8127, test stand) as described above. Scanning electron microscopy (SEM)
[0345] Samples were prepared for SEM imaging by sputter coating with gold. Typically, 5 kV or 10 kV accelerating voltage was used and images were collected at x500, x1000 and x2500 magnifications using a secondary electron detector or a backscattered electron detector. Example 1
[0346] The XP / fine fiber / scrim media was constructed by combining: Synteq XP with a 10 micron efficiency rating as the efficiency layer TMA synthetic liquid medium ("10XP", Donaldson, Inc., Minneapolis, MN), a support layer (CEREX 23200, Cerex Advanced Fabrics, Inc., Cantoment, FL), and a continuous fine fiber layer deposited on the support layer using electrospinning. The continuous fine fiber layer (0.9 μm in diameter) was formed from SVP 651 (see Table 3). The efficiency layer was the most upstream layer; the continuous fine fiber layer was placed downstream of the efficiency layer; and the support layer (scrim) was placed downstream of the continuous fine fiber layer.
[0347] The layers are placed on top of each other and placed in a filter housing.
[0348] Beta ratio versus particle size was measured under steady flow conditions (as described in the Steady Flow Conditions test) or under circulating flow conditions (as described in the Cyclic Flow Conditions test) for the following: Synteq XP with 10 micron efficiency rating TM Synthetic liquid media (“10XP”, Duramax P164378, Donaldson Co., Minneapolis, MN), Synteq XP with 5-micron efficiency rating TM Synthetic liquid media ("5XP", Duramax P165332, Donaldson Co., Minneapolis, MN), and XP / fine fiber / scrim media. The results are shown in FIG3 .
[0349] Although the Synteq XP with a 5-micron efficiency rating was observed TM The synthetic liquid media and the XP / fine fiber / scrim media were comparable in efficiency, but the XP / fine fiber / scrim media showed improved pressure drop, e.g. Figure 3B as shown in . The physical properties of SVP 651 resin reported in Table 3 are: Example 2
[0350] XP / fine fiber / scrim media was constructed as described in Example 1. XP / fine fiber / scrim media and Synteq XP with 10 micron efficiency rating TM Synthetic liquid media (Donaldson Co., Minneapolis, MN) was placed on a wire support and pleated to form a filter element. The filter element was then tested under steady flow conditions (as described in the steady flow condition test) or under cyclic flow conditions (as described in the cyclic flow condition test). The results are shown in Figure 4 (steady flow conditions) and Figure 5(Circulation flow conditions) are shown.
[0351] Synteq XP without fine fiber layer under steady flow conditions TM The synthetic liquid media achieved a reduction in the International Organization for Standardization (ISO) cleanliness code (measured and defined as described in ISO 4406:2017) (from 22 / 21 / 17 to 18 / 14 / 4), and the addition of the fine fiber layer achieved a further reduction in the cleanliness code (to 14 / 8 / 3), with comparable pressure drops - i.e., the pressure drop of the filter element including the XP / fine fiber / scrim media was 1 / 2 of that of the filter element including the Synteq XP without the fine fiber. TM The pressure drop of filter elements with synthetic liquid media is within 20%, and typically within 10%.
[0352] Synteq XP without fine fiber layer under dynamic flow conditions TM The synthetic liquid media achieved a reduction in the cleanliness code (from 22 / 21 / 17 to 22 / 18 / 8), but the addition of the fine fiber layer achieved a much greater reduction in the cleanliness code (22 / 21 / 17 to 18 / 14 / 4), achieving the same levels achieved without the fine fibers under steady flow conditions, again with comparable pressure drops. Example 3
[0353] The media were prepared according to Hanging Drop Sample Preparation Method 3, Table 1 Group A (small fines deposited directly on the scrim) and Hanging Drop Sample Preparation Method 4, Table 1 Group A (small fines deposited on a layer of large fines deposited on a scrim).
[0354] An exemplary image of a large fine fiber layer deposited on a scrim is shown in Figure 2B Shown in.
[0355] An exemplary image of small fibers deposited directly on the scrim is shown in Figure 2C and an exemplary image of small fine fibers deposited on a layer of large fine fibers deposited on a scrim is shown in Figure 2D (Small fine fibers are deposited on a layer of large fine fibers deposited on a scrim). Example 4
[0356] The medium was prepared according to the hanging drop sample preparation method 1. The theoretical basis weight of the obtained nonwoven was 1.64 g / m 2 .
[0357] The theoretical basis weights of the control nonwoven media (prepared by co-spinning each single electrospinning precursor solution from two different syringes) were 0.56 g / m for Solution 1 and Solution 2, respectively. 2 or 1.08g / m 2 .
[0358] The SEM images of the obtained medium are Figure 2E Shown in. Example 5
[0359] The sample integrity of the composite samples was evaluated during FHAST bench testing at up to 20 psi (at a headwind velocity of 0.56 ft / min, as further described in the Liquid Filtration Performance Test Method), and the initial pressure drop of each composite was plotted against the composite maximum pore size. As used in this example, "composite" refers to any fine fiber layer (including, for example, a first fine fiber layer, a second fine fiber layer, etc.) and a support layer. The composite includes at least one fine fiber layer.
[0360] The composite mean maximum pore size (P100) and the composite mean flow pore size (P50) of each sample were measured by flow porosimetry according to Flow Porosimetry Method A.
[0361] Each sample includes fine fibers of mixed diameters and a substrate. Some samples include a layer of fine fibers (these fine fibers include "large" fine fibers and "small" fine fibers), prepared as described in Methods 1, 2, or 3. Some samples include a first continuous fine fiber layer and a second continuous fine fiber layer, wherein the first continuous fine fiber layer includes fine fibers whose average diameter is at least three times the average fiber diameter of the smallest fibers of the second continuous fine fiber layer, prepared as described in Methods 4, 5, 6, or 7.
[0362] The results are shown in Figure 6. Triangles represent samples that maintained the structural integrity of the fine fibers throughout the FHAST bench test; squares represent samples that suffered fine fiber bursting (indicated by beta collapse) during the FHAST bench test. Samples that included two fine fiber layers are indicated by filled shapes, with the first layer including fine fibers having an average diameter that was at least three times the average fiber diameter of the smallest fibers of the second fine fiber layer. Samples that included one fine fiber layer (including fibers of mixed diameters) are indicated by unfilled shapes.
[0363] Most media samples with only one fine fiber layer (ie, prepared using Methods 1, 2, or 3) exhibited fine fiber damage (represented by open squares).
[0364] Only a few media samples with one fine fiber layer withstood pressures up to 20 psi (indicated by the open triangles) during the FHAST station testing of the layers. Without wishing to be bound by theory, it is believed that these fine fiber layers withstood the test because the coverage (basis weight) was very high—but such a high basis weight came at the expense of a higher initial pressure drop.
[0365] In contrast, all media samples prepared using Methods 4, 5, 6, or 7 and including two fine fiber layers maintained the structural integrity of the fine fibers (indicated by the filled triangles).
[0366] The results show that the average maximum pore size of the composites ( Fig. 6A ) and the average flow pore size of the composite material ( Figure 6B ) are both related to the ability of the composite to withstand the FHAST bench test (a laboratory test that highly correlates with the ability of a composite to withstand at least a 20 psi pressure drop during liquid filtration, which indicates better filter performance than filter media that cannot withstand the same conditions).
[0367] While some media samples with composite average maximum pore sizes (P100) up to 20 μm withstood the FHAST bench testing, a transition region was observed for media samples with composite average maximum pore sizes between 14 μm and 20 μm where some media samples began to fail.
[0368] Similarly, while some media with composite mean flow pore sizes (P50) up to 11 μm withstood the FHAST bench testing, a transition region was observed for media samples with composite mean maximum pore sizes between 6 μm and 11 μm where some media samples began to fail.
[0369] For example, samples without large fine fiber support with a composite average maximum pore size of 11 μm were unable to survive the FHAST bench test, while samples with large fine fiber support with a composite average maximum pore size of 11 μm were able to survive the FHAST bench test. Being able to use fine fiber samples with larger pore sizes allows fine tuning of efficiency without adverse pressure drop in the resulting composite. Example 6
[0370] Composite materials including a fine fiber layer and a support layer were prepared according to hanging drop sample preparation methods 8A-8C to form fine fiber sample A, fine fiber sample B, and fine fiber sample C (each of these fine fiber samples also included a support layer, as described above).
[0371] The efficiency layer was prepared as described in the Preparation of Media Handsheets section, which included 40 wt-% glass fiber (Lauscha B-10-F, nominal fiber diameter 1 μm, Lauscha Fiber International (Lauscha, Germany)) and 60 wt-% bicomponent fiber (Teijin TJ04CN, Teijin Limited (Tokyo, Japan)) to form efficiency layer A.
[0372] Capillary flow porometry measurements were performed on Fine Fiber Sample A, Fine Fiber Sample B, Fine Fiber Sample C, and Efficiency Layer A according to Flow Porometry Method B. The results are shown in Tables 4 and Figure 7 Shown in. Table 4.
[0373] The media was prepared as described in the Preparation of Media Handsheets section, which included 40 wt-% glass fibers (Lauscha B-26-R, nominal fiber diameter 2.4 μm, Lauscha Fiber International (Lauscha, Germany)) and 60 wt-% bicomponent fibers (Teijin TJ04CN, Teijin Limited (Tokyo, Japan)) to form load-bearing layer A.
[0374] The performance of the filter media including both the load layer A and the efficiency layer A was evaluated under both steady flow conditions and circulating flow conditions. The results are shown in Table 5A. As can be seen from the results in Table 5A, although the load layer and the efficiency layer have good performance (as indicated by the low pressure drop (ΔP)) under steady flow conditions and high efficiency under circulating flow conditions without the fine fiber layer, the efficiency drops sharply. Although the media can filter particles with a diameter of 10 μm with high efficiency under steady flow conditions, the efficiency for particles of the same diameter is more than 50 times lower under circulating flow conditions. Similarly, although the media can filter 99% of particles with a diameter of 9.3 μm under steady flow conditions, the same 99% filtration cannot be achieved under circulating flow conditions unless the particle diameter is 27 μm.
[0375] As shown in Table 5B, the addition of certain fine fiber layers (fine fiber sample A, fine fiber sample B) can "rescue" this efficiency loss while maintaining an acceptable pressure drop. In contrast, the addition of fine fiber sample C results in an undesirably high pressure drop (3x greater than the pressure drop exhibited by load layer A and efficiency layer A alone). The pores of fine fiber sample C are smaller than those of efficiency layer A, so that the P95 of fine fiber sample C (4.39 μm) does not fall within the P5-P50 range (4.70 μm to 8.82 μm) of efficiency layer A. In contrast, the P95 of both fiber sample A and fine fiber sample B falls within the P5-P50 range (4.70 μm to 8.82 μm) of efficiency layer A.
[0376] Having very small pore sizes in the fine fiber layer (as in, for example, fine fiber sample C) results in increased pressure drop because the fine fibers prevent air from flowing through the filter media. Additionally, without wishing to be bound by theory, it is believed that making the pore size of the fine fiber layer much smaller than the pore size of the efficiency layer is also less efficient because the fine fiber layer captures particle sizes that cannot be captured in the efficiency layer. In contrast, when the pore sizes of the fine fiber layer and the efficiency layer overlap, particle sizes captured by the fine fiber layer may also be captured by the efficiency layer. Table 5A. Test conditions Filter media layer Effective ΔP <![CDATA[Total β 10μm > β100 Stable flow Load Tier A / Efficiency Tier A 7.6kPa 152 9.3μm Circulation Load Tier A / Efficiency Tier A 7.2kPa 2.39 27μm Table 5B Test conditions Filter media layer Effective ΔP <![CDATA[Total β 10μm > β100 Circulation Loading layer A / Efficiency layer A / Fine fiber sample A 10.3kPa 8.53 17μm Circulation Loading layer A / efficiency layer A / fine fiber sample B 15.8kPa 129 9.5μm Circulation Loading layer A / Efficiency layer A / Fine fiber sample C 23.2kPa 2470 4.1μm Example 7
[0377] Samples prepared according to method 9 were analyzed according to the "thickness of fine fiber layer" method. Example images are shown in Fig. 8A , where the entire depth of the fine fiber layer is visible in cross section, while the fibers of the support layer are partially visible at the bottom of the image.
[0378] Figure 8B The marking of a thin fiber cross section using the polygon tool is shown. Figure 8C The image is shown after the area outside the selected thin fiber cross section has been cleared. Fig.8D The area of the selected thin fiber cross section is shown after recoloring it to white (to compensate for the fibers on the border of the selected section) using the threshold level tool, and the dashed line indicates the maximum thickness measured and recorded in the image (5.97 μm). Five of these maximum values were rounded to the nearest tenth of a micron, and then the rounded values were averaged. The results are shown in Table 6. Table 6 Maximum thickness (μm) rounding Sample 1 5.97 6 Sample 2 8.17 8.2 Sample 3 7.203 7.2 Sample 4 6.941 6.9 Sample 5 4.702 4.7 Average thickness of fine fiber layer 6.6
[0379] The complete disclosures of all patents, patent applications and publications cited herein and electronically available materials are incorporated by reference. In the event of any inconsistency between the disclosure of the present application and the disclosure of any document incorporated herein by reference, the disclosure of the present application shall prevail. The foregoing detailed description and examples are provided only for clear understanding. No unnecessary limitations should be understood therefrom. The present invention is not limited to the exact details shown and described, and variations apparent to those skilled in the art will be included in the present invention defined by the claims.
Claims
1. A filter medium comprising: Support layer; Continuous fine fiber layer with a thickness of up to 50 μm; as well as Efficiency layer; wherein the composite material comprising the support layer and the continuous fine fiber layer has a P95 / P50 ratio of up to 1.8, up to 1.9, or up to 2; wherein the P95 / P50 ratio of the efficiency layer is at least 1.8, at least 1.9, or at least 2; and Therein, the P95 value of the composite material falls within the range provided by the P5 and P50 values of the efficiency layer.
2. The filter medium of claim 1, wherein: The filter media further includes a second efficiency layer.
3. The filter medium of claim 2, wherein: The second efficiency layer is adjacent to and upstream of the efficiency layer.
4. The filter medium according to any one of claims 1 to 3, wherein The efficiency layer includes bicomponent fibers and efficiency fibers, wherein the efficiency fibers have a smaller diameter than the bicomponent fibers.
5. The filter medium according to any one of claims 1 to 3, wherein: The continuous fine fiber layer includes fibers having a diameter of up to 10 micrometers (μm).
6. The filter medium according to any one of claims 1 to 3, wherein: The continuous fine fiber layer includes fibers having an elliptical shape.
7. The filter medium of claim 1, wherein: The continuous fine fiber layer includes a mixture of fibers of different diameters.
8. The filter medium of claim 7, wherein: The fibers of different diameters are intermixed within a single layer of the continuous fine fiber layer.
9. The filter medium according to claim 7 or 8, wherein: The fibers of different diameters form different layers in the continuous fine fiber layer.
10. A filter element comprising the filter medium of any preceding claim.
